Creep resistant polyester composition

By using aluminum salts of general formula (I) and organic phosphonates in polyester materials, combined with glass fiber fillers, the flame retardancy, electrical trace resistance and mechanical properties of polyester materials in the prior art are solved. Polyester materials with high IZOD impact intensity and laser transmittance meet the flame retardant performance of UL94 V-0 grade.

CN119156420APending Publication Date: 2024-12-17ENVALIOR DEUTSCHLAND GMBH
View PDF 15 Cites 0 Cited by

Patent Information

Application Number
CN202280095878.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-05-12
Filing Date
2022-11-07
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

The prior art is difficult to develop a polyester-based thermoplastic molding material that is flame retardant, electrically trace-resistant and has good mechanical properties without the use of polyolefins and barium sulfate, especially without affecting the laser transmittance. , and it is difficult to achieve flame retardant performance of UL94 V-0 grade.

Method used

Using the aluminum salt of general formula (I), combined with organic phosphinate and phosphinate, and combined with glass fiber filler, the high IZOD impact intensity and laser transmittance are prepared through specific mass fraction ratios and processing methods. polyester composition.

Benefits of technology

Achieved polyester materials with high IZOD impact strength, good trace resistance and high laser transmittance without using polyolefins and barium sulfate, and maintaining UL94 V-0 grade under more demanding test conditions flame retardant properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119156420A_ABST
    Figure CN119156420A_ABST
Patent Text Reader

Abstract

The invention relates to the use of an aluminum salt of an organophosphorus compound according to formula (I) in or for a polyester-based product to achieve a CTI A of 600 according to IEC 60112-2010, the invention also relates to flame-retardant and creep-resistant polyester-based compositions based on at least one polyester, comprising at least one aluminum salt of an organophosphorus compound of general formula (I) and at least one organic phosphinic acid salt and / or at least one diphosphinic acid salt, and to articles produced therefrom, and to a method for the production thereof. # imgabs0 #
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an aluminum salt of an organic phosphorus compound of formula (I)

[0002]

[0003] Use in polyester-based products or for such products to achieve a CTIA of 600 according to IEC 60112-2010, as well as flame-retardant and tracking-resistant polyester-based compositions based on at least one polyester comprising at least one aluminum salt of an organic phosphorus compound of the general formula (I) and at least one organic phosphinate and / or at least one diphosphinate, and products producible therefrom, and methods for their production. Background Art

[0004] Polyesters, preferably polyalkylene terephthalates or polycycloalkylene terephthalates, and in particular polybutylene terephthalate (PBT), are important materials, for example, for motor vehicles, for components for the electrical and electronics industry or for household appliances, owing to their good mechanical stability, their low water absorption and their good processability. Particularly noteworthy are also the excellent electrical insulation properties which, unlike, for example, polyamides, are largely maintained even at elevated operating temperatures and in the presence of moisture, which is particularly relevant for use in fast-charging electric vehicles. In polyester applications near electrically conductive components, flame-retardant materials are often used in order to thus prevent the risk of fire caused by overheated wires or contacts. Good self-extinguishing properties are particularly desirable. Characteristics, specifically UL94 V-0 rating according to Underwriters Laboratories Inc. safety standard, "Test for Flammability of Plastic Materials for Parts in Devices and Appliances", pages 14 to 18, Northbrook 1998.

[0005] Besides the current increasing demand for the use of halogen-free flame retardants for environmental reasons, in industrial applications the properties sought in polyester-based products include high impact toughness as well as strength and stiffness, relatively low density and relatively high tracking resistance (according to IEC 60112-2010).

[0006] The desire for maximum design freedom and therefore for higher complexity of component geometries, together with the cost-driven need for automation-friendly and easily integrated mass production processes, ideally also requires materials that can be joined to one another by laser transmission welding [https: / / de.wikipedia.org / wiki / Laserdurchstrahlschwei%C3%9Fen]. For the laser-transmitting joining partners, this requires high laser transmittance at the employed laser wavelength. The latter is a great challenge, especially for products based on flame-retardant polyesters, since flame retardants specifically scatter or even absorb laser light, for example, with some nitrogen-containing flame retardant synergists, but also specifically with antimony trioxide, since antimony trioxide is often used as a synergist for halogen-containing flame retardants.

[0007] Prior art

[0008] In Table 4, WO 2021 / 076169 A1 discloses a polymer composition comprising polybutylene terephthalate, glass, aluminum methylphosphonate and melam.

[0009] In Example 4, DE 10 2017 215776 A1 teaches a composition comprising 50% by weight of polybutylene terephthalate, 30% by weight of glass fibers and 20% by weight of the flame retardant combination FM 4, which consists of an aluminum salt of diethylphosphinic acid containing 10 mol % of aluminum ethylbutylphosphinate and 5 mol % of aluminum ethylphosphonate produced by a process according to US 7,420,007 B2.

[0010] WO 2012 / 139990 A1 discloses tracking-resistant, flame-retardant, reinforced thermoplastic molding materials based on polyalkylene terephthalates, which, in addition to a flame retardant consisting of a nitrogen- or phosphorus-containing compound, also contain polyolefins from the group consisting of polyethylene, polypropylene and polypropylene copolymers. Despite these features, which have an increased tracking resistance, the use of polyolefins as additional polymers carries the risk of reducing the typical advantages of polyalkylene terephthalates, in particular the high surface tension and the high color stability under thermal stress, especially since the use of polyolefins, in particular polyethylene, in polyalkylene terephthalate formulations also leads to an increased risk of residues in the injection mold.

[0011] EP 3 067 388 A1 discloses a flame-retardant molding material based on polyester containing aluminum tris(diethylphosphinate) and melamine cyanurate, wherein the addition of barium sulfate achieves an improvement in tracking resistance. However, the addition of solids such as barium sulfate, which are not meltable under injection molding conditions, leads to deterioration of mechanical properties and reduced laser transmittance, which is undesirable in particular in applications that can be laser transmission welded. In addition, in the case of PBT, EP 3 067 388 A1 is only able to achieve a V-1 rating according to UL 94.

[0012] Starting from the prior art, the object of the present invention is to provide a flame-retardant, tracking-resistant and glass-fiber-reinforced polyester-based thermoplastic molding material to achieve good mechanical properties while achieving a V-0 rating according to UL94 at a wall thickness of not more than 0.8 mm without the use of polyolefins and barium sulfate and preferably without the use of nitrogen-containing synergists, in particular melamine-based synergists. According to the invention, improved tracking resistance is understood to mean that a CTI A of 600 according to IEC 60112-2010 is achieved. Ideally, this improved tracking resistance should not have an adverse effect on the laser transmittance and therefore not hinder or make it impossible to use for laser transmission welding. In the context of the present invention, good mechanical properties are especially indicated by high values ​​of the IZOD impact strength determinable according to DIN EN ISO 180.

[0013] It has now surprisingly been found that phosphorus-containing aluminum salts of the general formula (I)

[0014]

[0015] Where R represents C1-C 12 -alkyl, a CTI A of 600 according to IEC 60112-2010 is achieved in polyester-based products, and when the mass fraction of the aluminum salt of the general formula (I) is less than the mass fraction of the organic metal phosphinate or diphosphinate that can be used, together with at least one organic metal phosphinate or diphosphinate, the complex objectives of the invention with respect to flame retardancy, mechanical properties and also in particular laser transparency are achieved in reinforced polyester-based compositions and products producible therefrom.

[0016] It was also surprisingly found that the phosphorus-containing aluminum salts of the general formula (I) made it possible to deviate from standard IEC 60112-2010 so that instead of testing with 50 droplets on 5 test specimens in each case (250 droplets), the test was carried out even more stringently with 100 droplets on 3 test specimens in each case (300 droplets in total), and the average number of droplets leading to material failure due to tracking currents > 0.5 A or ignition and subsequent continuous ignition on the polyester-based test specimens was significantly higher than in the comparative examples without the phosphorus-containing aluminum salt of the general formula (I).

[0017] IZOD Impact Strength

[0018] The IZOD impact strength according to DIN EN ISO 180 used in the context of the present invention for obtaining the mechanical parameters can be used not only for rigid thermoplastic injection molding and extrusion molding materials, thermosetting materials and thermotropic liquid crystal polymers, but also for filled and reinforced materials. According to the following equation, the impact energy E absorbed during the fracture of the unnotched test specimen C Related to the initial cross-sectional area of ​​the test specimen:

[0019]

[0020] where a iU = impact strength, h = thickness and b = width.

[0021] The test specimens that can be used here can be produced according to the corresponding molding material standards or by compression and injection molding, or they can be collected from multi-purpose test specimens (DIN EN ISO 527 [2]). According to DIN EN ISO 3167, type A, the dimensions of the unnotched test specimens used in the context of the present invention are: length l = (80 ± 2) mm; width b = (10.0 ± 0.2) mm; thickness h = (4.0 ± 0.2) mm. https: / / wiki.polymerservice-merseburg.de / index.php / Schlagbiegeversuch

[0022] Laser transmittance

[0023] According to the invention, a high laser transmittance is understood to mean a transmittance of at least 8%, preferably at least 9%, measured at a laser wavelength of 980 nm on a plate with a thickness of 1.5 mm using an LPKF TMG3 transmittance meter from LPKF Laser & Electronics AG (Garbsen, Germany). The transmittance meter LPKF TMG3 is a certified, traceably calibrated measuring instrument. Its performance was confirmed in the context of a statistical measurement system analysis (MSA). The instrument also meets the specifications of the automotive standard IATF 16949 and is therefore directly eligible for quality assurance in accordance with the standard. Based on DVS Guideline 2243 (01 / 2014) "Laser beam welding of thermoplastic materials (Laserstrahlschweiβen thermoplastischer Kunststoffe)", the measurements in the context of the present invention were carried out in the near infrared (NIR) range using test specimens with dimensions of 125 mm×13 mm×1.5 mm. Prior to the measurement, the transmission measuring instrument LPKF TMG3 from LPKF Laser & Electronics AG was calibrated with a measurement standard produced in accordance with DIN EN ISO / IEC 17025. In the context of the present invention, the measurements were carried out at a laser wavelength of 980 nm.

[0024] Tracking resistance

[0025] According to https: / / de.wikipedia.org / wiki / kriechstromfestigkeit, tracking resistance describes the dielectric strength of the surface (tracking path) of an insulating material, especially when exposed to moisture and contaminants. It defines the maximum tracking current that may occur under standardized test conditions (predetermined voltage, conductive layer material) in a defined test configuration (electrode distance, electrode shape). Tracking resistance is reported as a CTI value (relative tracking index). The CTI value represents the voltage in volts (V) until the material under investigation shows no tracking when 50 drops of a standardized electrolyte solution (A or B, KA or KB value respectively) are applied. The measurement is carried out on the surface and the drops are dripped between two platinum electrodes every 30+ / -5 seconds. The failure criterion is a tracking current >0.5A or a component ignition. Detailed information on the measurement method of the CTI value is specified in IEC 60112.

[0026] The polyester-based composition according to the invention should ultimately also show a V-0 class at a maximum thickness of 0.8 mm determinable according to method UL94V (Underwriters Laboratories Safety Standard, "Tests for Flammability of Plastic Materials for Parts of Equipment and Appliances", pages 14 to 18, Northbrook 1998), taking into account the UL94 V-0 class specified in WO 2021 / 076169 A1, or at least show no significant reduction compared to the prior art.

[0027] In the context of the present invention, "alkyl" is understood to mean a straight or branched saturated hydrocarbon group. In some embodiments, an alkyl group having 1 to 6 carbon atoms is used. This may be referred to as a "lower alkyl group". Preferred alkyl groups are methyl (Me), ethyl (Et), propyl (specifically n-propyl and isopropyl), butyl (specifically n-butyl, isobutyl, sec-butyl, tert-butyl) and pentyl (specifically n-pentyl, isopentyl, neopentyl) and hexyl, etc. The term polyalkylene is similarly defined.

[0028] For the sake of clarity, it should be noted that the scope of the present invention includes all the specifically stated definitions and parameters listed generally or in any desired combination within the preferred range. This relates in particular to the mass fractions specifically stated for the composition according to the invention, the uses described according to the invention and the methods described according to the invention. The standards mentioned within the scope of this application refer to the versions applicable at the time of the application date of the present invention. Aryl (Ar for short) is an organic chemical group with an aromatic basic structure. Therefore, aryl is a general description of a monovalent atomic group derived from aromatic hydrocarbons by removing hydrogen atoms bonded to the ring. Most aryls are derived from benzene (C6H6), and the simplest aryl is phenyl (Ph) (-C6H5). Aryl can exist as a fragment of a molecule or as an unstable free radical. Summary of the invention

[0029] The present invention provides the use of the aluminum salt of general formula (I),

[0030]

[0031] Where R represents C1-C 12-alkyl, preferably represents methyl, ethyl, isopropyl or isobutyl, tert-butyl or n-butyl, particularly preferably represents ethyl or methyl, very particularly preferably represents methyl, in order to achieve a CTIA of 600 according to IEC 60112-2010 in or for a product based on polyester, preferably for or for a product based on polyalkylene terephthalate or polycycloalkylene terephthalate, in particular for or in a product based on polybutylene terephthalate (PBT), polyethylene terephthalate (PET) or poly-1,4-cyclohexanedimethanol terephthalate. For the sake of clarity, it should be noted that the terms polybutylene terephthalate (PBT)-, polyethylene terephthalate (PET)- or poly-1,4-cyclohexanedimethanol terephthalate-based products are synonymous with the terms polybutylene terephthalate (PBT)-, polyethylene terephthalate (PET)- or poly-1,4-cyclohexanedimethanol terephthalate-based products.

[0032] First, the present invention relates to a composition comprising:

[0033] A) per 100 parts by mass of polyalkylene terephthalate or polycycloalkylene terephthalate,

[0034] B) 1 to 80 parts by mass, preferably 2 to 60 parts by mass, particularly preferably 3 to 30 parts by mass, and especially preferably 5 to 20 parts by mass of at least one aluminum salt of the general formula (I)

[0035]

[0036] Where R represents C1-C 12 - alkyl, preferably represents methyl, ethyl, isopropyl or isobutyl, tert-butyl or n-butyl, particularly preferably represents ethyl or methyl, very particularly preferably represents methyl,

[0037] and

[0038] C) 5 to 120 parts by mass, preferably 7 to 80 parts by mass, particularly preferably 8 to 60 parts by mass, especially preferably 10 to 50 parts by mass of at least one organic phosphinate of the formula (II) and / or at least one diphosphinate of the formula (III) and / or polymers thereof,

[0039]

[0040] in

[0041] R 1 , R 2 are identical or different and represent a linear or branched C1-C6-alkyl group and / or represent a C6-C 14 - aryl,

[0042] R 3 Represents linear or branched C1-C 10 -alkylene, C6-C 10 -arylene or C1-C6-alkyl-C6-C 10 -Arylene or C6-C 10 - aryl-C1-C6-alkylene,

[0043] M stands for aluminum, zinc or titanium,

[0044] m represents an integer from 1 to 4,

[0045] n represents an integer from 1 to 3,

[0046] x represents 1 and 2,

[0047] wherein n, x and m in formula (III) can simultaneously be integers only, so that the diphosphite of formula (III) is uncharged as a whole, and

[0048] D) 3 to 300 parts by mass, preferably 5 to 200 parts by mass, particularly preferably 10 to 120 parts by mass, and especially preferably 15 to 90 parts by mass of at least one glass-based filler and / or reinforcing agent,

[0049] The proviso is that component B) is present in a lower mass fraction than component C).

[0050] The invention also provides products based on the composition according to the invention, in particular for electric vehicles, for household appliances and for products in the electronic and electrical fields.

[0051] The preparation of a composition based on polyalkylene terephthalate or polycycloalkylene terephthalate, in particular a composition based on PBT, PET or poly-1,4-cyclohexanedimethanol terephthalate, for use in electric vehicle products, household appliances and the electronic and electrical fields is carried out by mixing the components A), B), C) and D) that can be used as starting materials in at least one mixing device in the above-mentioned mass fraction ratio. This mixing provides a molding material based on the composition according to the invention as an intermediate product. These molding materials can consist only of components A), B), C) and D), or additionally contain at least one other component E). In the case of a composition that provides laser transmission, the other component E) will be selected so as to avoid laser absorbing additives.

[0052] The present invention also provides a method for producing a product, preferably an electric vehicle, a household appliance, or a product in the electronic and electrical fields, the method comprising:

[0053] 100 parts by weight of component A) of polyalkylene terephthalate or polycycloalkylene terephthalate, specifically polybutylene terephthalate, polyethylene terephthalate or poly-1,4-cyclohexanedimethanol terephthalate,

[0054] B) 1 to 80 parts by mass, preferably 2 to 60 parts by mass, particularly preferably 3 to 30 parts by mass, and especially preferably 5 to 20 parts by mass of at least one aluminum salt of the general formula (I)

[0055]

[0056] Where R represents C1-C 12 - alkyl, preferably represents methyl, ethyl, isopropyl or isobutyl, tert-butyl or n-butyl, particularly preferably represents ethyl or methyl, very particularly preferably represents methyl,

[0057] and

[0058] C) 5 to 120 parts by mass, preferably 7 to 80 parts by mass, particularly preferably 8 to 60 parts by mass, especially preferably 10 to 50 parts by mass of at least one organic phosphinate of the formula (II) and / or at least one diphosphinate of the formula (III) and / or polymers thereof,

[0059]

[0060] in

[0061] R 1 , R 2 are identical or different and represent a linear or branched C1-C6-alkyl group and / or represent a C6-C 14 - aryl,

[0062] R 3 Represents linear or branched C1-C 10 -alkylene, C6-C 10 -arylene or C1-C6-alkyl-C6-C 10 -Arylene or C6-C 10 - aryl-C1-C6-alkylene,

[0063] M stands for aluminum, zinc or titanium,

[0064] m represents an integer from 1 to 4,

[0065] n represents an integer from 1 to 3,

[0066] x represents 1 and 2,

[0067] wherein n, x and m in formula (III) can simultaneously be integers only, so that the diphosphite of formula (III) as a whole is uncharged, and

[0068] D) 3 to 300 parts by mass, preferably 5 to 200 parts by mass, particularly preferably 10 to 120 parts by mass, and especially preferably 15 to 90 parts by mass of at least one glass-based filler and / or reinforcing agent,

[0069] and optionally mixing or blending with further additives in at least one mixing apparatus and finally processing the resulting mixture by injection molding, with the proviso that component B) is used in a lower mass fraction than component C).

[0070] Preferably, the components are kneaded, compounded, extruded or rolled into a molding material. Preferably, this mixing is carried out at a temperature in the range of 230° C. to 300° C., particularly preferably by compounding on a co-rotating twin-screw extruder or a Buss kneader. It may be advantageous to premix the individual components.

[0071] The injection molding process is characterized in that the raw material (preferably in the form of pellets) is melted (plasticized) in a heated cylindrical cavity and injected into the temperature-controlled cavity under pressure as an injection molding material. After the material cools (solidifies), the injection molded part is demoulded.

[0072] The difference is:

[0073] 1. Plasticization / melting

[0074] 2. Injection stage (filling operation)

[0075] 3. Holding stage (due to thermal shrinkage during crystallization)

[0076] 4. Demoulding.

[0077] The injection molding machine consists of a clamping unit, an injection unit, a drive and a controller. The clamping unit includes fixed and movable clamping plates, end plates and tie rods for the mold and a drive for the movable mold clamping plate (knee joint or hydraulic clamping unit).

[0078] The injection unit consists of an electrically heatable barrel, a drive for the screw (motor, transmission) and a hydraulic device for displacing the screw and the injection unit. The task of the injection unit is to melt, meter, inject and exert a holding pressure on the powder / granular material (due to shrinkage). The problem of melt backflow in the screw (leakage) is solved by a backflow baffle.

[0079] In the injection mold, the inflowing melt is subsequently separated and cooled, thus forming the product to be manufactured. For this purpose, two mold halves are always required. In injection molding, a distinction is made between the following functional complexes:

[0080] - Runner system

[0081] -Molded inserts

[0082] -exhaust

[0083] -Machine installation and force absorption

[0084] - Demolding systems and motion transfer devices (Bewegungsübertragung)

[0085] - Temperature control

[0086] The invention therefore also relates to products obtainable by injection moulding of the compositions according to the invention. DETAILED DESCRIPTION

[0087] In a further preferred embodiment, the present invention also relates to a composition and a product based thereon which comprises not only components A) to D), but also at least one further additive as component E), which is different from components B), C) and D), preferably in an amount of 0.01 to 100 parts by mass, particularly preferably in an amount of 0.05 to 50 parts by mass, very particularly preferably in an amount of 0.1 to 30 parts by mass, in each case based on 100 parts by mass of component A), with the proviso that laser-absorbing additives are avoided if laser transparency needs to be retained.

[0088] Component A)

[0089] The polyalkylene terephthalates or polycycloalkylene terephthalates that can be used as component A) according to the present invention can be produced by a variety of methods, synthesized from different units, and in specific use cases, alone or in combination with processing aids, stabilizers, polymer alloy partners (Legierungspartnern) (e.g., elastomers) or reinforcing materials (e.g., mineral fillers or glass fibers) and optional other additives, to make materials with a specifically regulated combination of properties. Blends with a certain proportion of other polymers are also suitable, wherein one or more compatibilizers can be used optionally. If necessary, the properties of the polymer can be improved by adding elastomers.

[0090] Preferred polyalkylene terephthalates or polycycloalkylene terephthalates are producible by known methods from terephthalic acid (or reactive derivatives thereof) and aliphatic or cycloaliphatic diols having 2 to 10 carbon atoms (Kunststoff-Handbuch, vol. VIII, p. 695-743, Karl Hanser Verlag, Munich 1973).

[0091] Preferred polyalkylene terephthalates or polycycloalkylene terephthalates contain at least 80 mol %, preferably at least 90 mol %, of terephthalic acid groups, based on the dicarboxylic acid, and at least 80 mol %, preferably at least 90 mol %, of 1,4-cyclohexanedimethanol and / or ethylene glycol and / or propane-1,3-diol (in the case of polypropylene terephthalate) and / or butane-1,4-diol groups, based on the diol component.

[0092] Preferred polyalkylene terephthalates or polycycloalkylene terephthalates may comprise not only terephthalic acid groups but also up to 20 mol % of groups of other aromatic dicarboxylic acids having 8 to 14 carbon atoms or groups of aliphatic dicarboxylic acids having 4 to 12 carbon atoms, in particular groups of phthalic acid, isophthalic acid, naphthalene-2,6-dicarboxylic acid, 4,4′-biphenyldicarboxylic acid, succinic acid, adipic acid, sebacic acid, azelaic acid, cyclohexanediacetic acid, cyclohexanedicarboxylic acid.

[0093] Preferred polyalkylene terephthalates or polycycloalkylene terephthalates may include not only 1,4-cyclohexanedimethanol / ethylene glycol / propane-1,3-diol / butane-1,4-diol, but also up to 20 mol % of other aliphatic diols having 3 to 12 carbon atoms or up to 20 mol % of alicyclic diols having 6 to 21 carbon atoms, preferably propane-1,3-diol, 2-ethylpropane-1,3-diol, neopentyl glycol, pentane-1,5-diol, hexane-1,6-diol, 3-methylpentane-2,4 ... 2,4-diol, 2,2,4-trimethylpentane-1,3-diol, 2,2,4-trimethylpentane-1,5-diol, 2-ethylhexane-1,3-diol, 2,2-diethylpropane-1,3-diol, hexane-2,5-diol, 1,4-di(β-hydroxyethoxy)benzene, 2,2-bis(4-hydroxycyclohexyl)propane, 2,4-dihydroxy-1,1,3,3-tetramethylcyclobutane, 2,2-bis(3-β-hydroxyethoxyphenyl)propane and 2,2-bis(4-hydroxypropoxyphenyl)propane.

[0094] Particularly preferred are polyalkylene terephthalates or polycycloalkylene terephthalates derived solely from terephthalic acid and its reactive derivatives (in particular its dialkyl esters), and 1,4-cyclohexanedimethanol and / or ethylene glycol and / or propane-1,3-diol and / or butane-1,4-diol, particularly preferably poly-1,4-cyclohexanedimethanol terephthalate, polyethylene terephthalate and polybutylene terephthalate and mixtures thereof.

[0095] Preferred polyalkylene terephthalates or polycycloalkylene terephthalates also include copolyesters produced from at least two of the above acid components and / or from at least two of the above alcohol components. A particularly preferred copolyester is polyethylene glycol / butane-1,4-diol terephthalate.

[0096] The polyalkylene terephthalates or polycycloalkylene terephthalates generally have a relative humidity of 30 to 150 cm, measured in each case at 25° C. in phenol / o-dichlorobenzene (1:1 parts by weight). 3 / g range, preferably between 40 and 130 cm 3 / g range, particularly preferably in the range of 50 to 100 cm 3 / g range. According to the Mark-Houwink-Gleichung equation, the intrinsic viscosity IV, also known as the Staudinger index or limiting viscosity, is proportional to the average molecular weight and is an extrapolation of the viscosity number VN for a polymer concentration of zero. It can be estimated from a measurement series or by using an appropriate approximation method (e.g., the Billmeyer method). VN [ml / g] is obtained by measuring the solution viscosity in a capillary viscometer (e.g., an Ubbelohde viscometer). Solution viscosity is a measure of the average molecular weight of a plastic. The dissolved polymer is measured using different solvents (formic acid, metacresol, tetrachloroethane, phenol, 1,2-dichlorobenzene, etc.) and concentrations. The viscosity number VN makes it possible to control the processing and use properties of the plastic. The thermal stress, aging process or the influence of chemicals, weathering and light on the polymer can be studied by comparative measurements. In the context of the present invention, the method is standardized for commonly used plastics according to DIN ISO 1628-5 for polyesters. See also: http: / / de.wikipedia.org / wiki / Viskosimetrie and "http: / / de.wikipedia.org / wiki / Mark-Houwink-Gleichung".

[0097] It is also possible to use them in a mixture with other polyesters and / or other polymers as polyalkylene terephthalates or polycycloalkylene terephthalates of component A) according to the invention.

[0098] The polyalkylene terephthalates or polycycloalkylene terephthalates which can be used as component A) can be mixed with conventional additives, in particular with release agents, in the melt during compounding, wherein the person skilled in the art understands "compounding" as a term from the plastics industry, synonymous with plastics processing, which describes the process of finishing plastics by mixing in additive substances (fillers, additives, etc.) in order to specifically optimize various properties. Compounding is preferably carried out in an extruder, particularly preferably in a co-rotating twin-screw extruder, a counter-rotating twin-screw extruder, a planetary screw extruder or a blender, and includes the process operations of conveying, melting, dispersing, mixing, degassing and pressurizing.

[0099] It is preferred when the polyester useful as component A) is a polyalkylene terephthalate or a polycycloalkylene terephthalate, particularly preferably polyethylene terephthalate (PET) [CAS No. 25038-59-9] or polybutylene terephthalate [CAS No. 24968-12-5], in particular polybutylene terephthalate (PBT).

[0100] Alternatively, the polyester which can be used as component A) is a polycycloalkylene terephthalate, in particular poly-1,4-cyclohexanedimethanol terephthalate [CAS No. 25037-99-4].

[0101] Component B)

[0102] As component B) which can be used according to the invention, preference is given to using aluminum salts of the general formula (I),

[0103]

[0104] Where R represents C1-C 12 -Alkyl preferably represents methyl, ethyl, isopropyl or isobutyl, tert-butyl or n-butyl, particularly preferably represents ethyl or methyl, very particularly preferably represents methyl.

[0105] These aluminum salts of organophosphorus compounds of the general formula (I) which can be used as component B) can be produced by different methods and synthesized from different units. In the context of the present invention, the production of compounds (Ia) which can be used preferably according to the invention, wherein R=methyl, utilizes the following process:

[0106]

[0107] 83 g of methylphosphonic acid are added to a reaction vessel and heated to 120° C. In the presence of water, an intermediate product produced by 50 g of methylphosphonic acid and 35.4 g of tri(isopropoxy)aluminum is added to the reaction vessel. Under mechanical stirring, the resulting solution containing methylphosphonic acid and methylphosphonic acid aluminum as intermediate products in a molar ratio of 5:1 is heated to 240° C. At 240° C., stirring is continued for about 30 minutes until a solid is formed. Then, 500 ml of water is added and the resulting mixture is stirred for 16 h to form a uniform slurry. Finally, the product is separated by filtration, washed with 750 ml of water and dried. This produces 64.3 g of the product of formula (Ia) (which is fine colorless crystals) which is most preferably used as component B) in a yield of 93%. The empirical formula (Ia) represents the repeating monomer unit (i.e., coordination unit) of the coordination polymer in crystalline form.

[0108] Further methods, in particular for the case where R≠methyl, can be derived from WO 2020 / 132075 A1, the content of which is incorporated into the present invention in its entirety.

[0109] Particularly preferred are components B) according to formula (Ia) having a molar ratio of phosphorus to aluminum of 4:1, determinable by ICP-OES elemental analysis, wherein needle-shaped crystals are particularly preferred. In this regard, see Example 1 in WO 2021 / 076169A1. For ICP-OES, see: https: / / www.itmc.rwth-aachen.de / go / id / gden

[0110] Component C)

[0111] As component C), the composition according to the invention comprises at least one phosphinate of the formula (II)

[0112]

[0113] and / or at least one diphosphite of formula (III)

[0114]

[0115] and / or polymers thereof. In the context of the present invention, the phosphinates of the formula (II) and the diphosphinates of the formula (III) are also referred to as phosphinates.

[0116] M in formula (II) or (III) preferably represents aluminum or zinc. 1 , R 2 It is preferred when R are identical or different and represent linear or branched C1-C6-alkyl and / or phenyl. 1 , R 2It is particularly preferred when are identical or different and represent methyl, ethyl, n-propyl, isopropyl, n-butyl, tert-butyl, n-pentyl and / or phenyl.

[0117] When R in formula (III) 3 When R represents methylene, ethylene, n-propylene, isopropylene, n-butylene, tert-butylene, n-pentylene, n-octylene, n-dodecylene, phenylene, naphthylene, methylphenylene, ethylphenylene, tert-butylphenylene, methylnaphthylene, ethylnaphthylene, tert-butylnaphthylene, phenylmethylene, phenylethylene, phenylpropylene or phenylbutylene, it is preferred. 3 When it represents phenylene or naphthylene, it is particularly preferred. Suitable phosphinates are described in WO-A97 / 39053, the content of which is incorporated into the present application for the phosphinates. In the context of the present invention, particularly preferred phosphinates are the aluminum and zinc salts of dimethylphosphinate, the aluminum and zinc salts of ethylmethylphosphinate, the aluminum and zinc salts of diethylphosphinate and the aluminum and zinc salts of methyl-n-propylphosphinate and mixtures thereof.

[0118] In the formula (II), m preferably represents 2 and 3, particularly preferably represents 3.

[0119] In the formula (III), n preferably represents 1 and 3, particularly preferably represents 3.

[0120] In the formula (III), x preferably represents 1 and 2, particularly preferably represents 2.

[0121] As component C), very particular preference is given to using aluminum tris(diethylphosphinate) [CAS No. 225789-38-8], which is marketed under the trade name OP1230 or OP1240 is available, for example, from Clariant International Ltd. Muttenz (Switzerland).

[0122] According to the invention, component B) is used in a lower mass fraction than component C).

[0123] Component D)

[0124] The polymer composition according to the invention comprises as component D at least one glass-based filler and / or reinforcing agent. It is also possible to use mixtures of two or more different glass-based fillers and / or reinforcing agents.

[0125] Preferably, glass according to DIN 1259-1 is used as component D). Very particular preference is given to using solid or hollow glass spheres, glass fibers, ground glass or aluminoborosilicate glass (E glass) having an alkali metal content of 1% [CAS No. 65997-17-3].

[0126] Considering the glass fibers that can preferably be used according to the invention, the person skilled in the art distinguishes according to "http: / / de.wikipedia.org / wiki / Faser-Kunststoff-Verbund" between short-cut fibers (also called short fibers) with a length in the range of 0.1 to 1 mm, long fibers with a length in the range of 1 to 50 mm and continuous fibers with a length L>50 mm. Short fibers are preferably used in injection molding and are suitable for direct processing with an extruder. Long fibers are likewise processable in an extruder. Continuous fibers are used as rovings or fabrics in fiber-reinforced plastics. Products containing continuous fibers achieve the highest rigidity and strength values. In addition, ground glass fibers are provided, the length of which after grinding is generally in the range of 70 to 200 μm.

[0127] Glass fibers which can particularly preferably be used as component D) according to the invention are chopped long glass fibers having an average initial length in the range from 1 to 50 mm, particularly preferably in the range from 1 to 10 mm, very particularly preferably in the range from 2 to 7 mm, the initial length being the length before any processing, in particular before processing in a compounder.

[0128] Preferred glass fibers which can be used as component D) have an average fiber diameter in the range of 7 to 18 μm, particularly preferably in the range of 9 to 15 μm. A possible method for determining the fiber diameter that can be used is scanning electron microscopy (SEM) (https: / / de.wikipedia.org / wiki / Rasterelektronenmikroskop).

[0129] In a preferred embodiment, the glass fibers, which can preferably be used as component D), are treated with a suitable sizing system or tackifier / tackifier system. Preferably, silane-based sizing systems / tackifiers are used. Particularly preferred silane-based tackifiers for treating glass fibers, which can preferably be used as component D), are silane compounds of the general formula (IV):

[0130] (X-(CH2) q ) k -Si-(O-CrH 2r+1 ) 4-k (IV)

[0131] in

[0132] X represents NH2, carboxyl, HO or

[0133] q in formula (IV) represents an integer from 2 to 10, preferably from 3 to 4,

[0134] r in formula (IV) represents an integer from 1 to 5, preferably from 1 to 2, and

[0135] k in formula (IV) represents an integer of 1 to 3, preferably 1.

[0136] Particularly preferred adhesion promoters are silane compounds from the group consisting of aminopropyltrimethoxysilane, aminobutyltrimethoxysilane, aminopropyltriethoxysilane, aminobutyltriethoxysilane and the corresponding silanes which contain a glycidyl group or a carboxyl group as substituent X in formula (IV), the carboxyl group being very particularly preferred.

[0137] The treatment of the glass fibers which can preferably be used as component D) comprises the use of adhesion promoters, preferably silane compounds of the formula (IV), preferably in an amount of 0.05 to 2% by weight, particularly preferably in an amount of 0.25 to 1.5% by weight and very particularly preferably in an amount of 0.5 to 1% by weight, in each case based on 100% by weight of component D).

[0138] Due to the processing of the composition or product, the glass fibers which can preferably be used as component D) in the composition or product can be shorter than the glass fibers originally used. Therefore, the arithmetic mean value of the glass fiber lengths which can be determined by high-resolution X-ray computed tomography after processing is usually only in the range of 150 μm to 300 μm.

[0139] According to "http: / / www.rg.de / wiki / Glasfasern", glass fibers are produced by melt spinning (die drawing, rod drawing and die blowing). In the die drawing process, the hot glass composition flows through hundreds of holes of a platinum spinning plate under the influence of gravity. The base filament can be drawn out at a speed of 3-4 km / min with unlimited length.

[0140] A person skilled in the art distinguishes between various types of glass fibers, some of which are listed below, for example:

[0141] E-glass, the most commonly used material with the best price / performance ratio (E-glass from R&G) and according to https: / / www.rg.de / wiki / Glasfasern has the following composition: 53-55% SiO2, 14-15% Al2O3, 6-8% B2O3, 17-22% CaO, <5% MgO, <1% K2O / Na2O and about 1% of other oxides;

[0142] H glass, hollow glass fiber for weight reduction (R&G hollow glass fiber fabric, 160g / m 2 and 216g / m 2 )

[0143] R, S glass for increased mechanical requirements (S2 glass from R&G)

[0144] D glass, borosilicate glass for enhanced electrical requirements;

[0145] C glass, with improved chemical resistance;

[0146] ·Quartz glass, high temperature resistance.

[0147] Further examples can be found at "http: / / de.wikipedia.org / wiki / Glasfaser". For plastic reinforcement, E-glass fibers have reached the most important position. The "E" in E-glass stands for electrical glass, since it was originally used, inter alia, in the electrical industry.

[0148] For the production of E glass, a glass melt is produced from pure quartz to which limestone, kaolin and boric acid are added. In addition to silicon dioxide, they contain various metal oxides in different amounts. The composition determines the properties of the product. According to the present invention, it is preferred to use at least one type of glass fiber from the group of E glass, H glass, R, S glass, D glass, C glass and quartz glass, and it is particularly preferred to use glass fibers made of E glass.

[0149] Glass fibers made of E-glass are the most widely used reinforcement material. The strength properties correspond to those of metals (e.g. aluminum alloys), and the specific gravity of laminates containing E-glass fibers is less than that of metals. E-glass fibers are non-combustible, heat-resistant up to about 400° C., and resistant to most chemical and weathering influences.

[0150] However, preference is also given to using as component D) non-fibrous and non-foamed ground glass having a particle size distribution determinable by laser diffraction in accordance with ISO 13320 with a d90 value in the range of 5 to 250 μm, preferably in the range of 10 to 150 μm, particularly preferably in the range of 15 to 80 μm, very particularly preferably in the range of 16 to 25 μm. With regard to d90 values, their determination and their meaning, reference is made to Chemie Ingenieur Technik (72) p. 273-276, 3 / 2000, Wiley-VCH Verlags GmbH, Weinheim, 2000, according to which the d90 value is the particle size below which 90% of the particles lie.

[0151] According to the invention, preference is given to granular, non-cylindrical, non-fibrous and non-foamed ground glasses which have an aspect ratio determinable by scanning electron microscopy of less than 5, preferably less than 3 and particularly preferably less than 2. This obviously does not include the value zero.

[0152] In one embodiment, the non-foamed and non-fibrous milled glass that can be used as component D) is also characterized in that it does not have the typical glass geometry of fiber glass, i.e., has a cylindrical or elliptical cross-section with an aspect ratio (L / D ratio) greater than 5, which can be determined by scanning electron microscopy.

[0153] In one embodiment, the non-foamed and non-fibrous ground glass that can be used as component D) according to the invention is preferably obtained by grinding the glass with a grinder, preferably with a ball mill, and particularly preferably by subsequent filtering / sieving. In one embodiment, the preferred starting materials for the grinding of the non-fibrous and non-foamed ground glass that can be used as component D) also include glass waste, such as glass waste produced as undesirable by-products and / or as unqualified products in the production of glass products. This especially includes waste glass, recycled glass and cullet, such as can be produced in particular in the production of window glass or bottle glass and in the production of glass-containing fillers and reinforcing agents, especially in the form of so-called frits. The glass can be colored, wherein uncolored glass is preferably used as the starting material used in component D).

[0154] Component E)

[0155] The component E) used is preferably selected from at least one other additive different from components B), C) and D), with the proviso that laser absorbing additives are avoided if laser transparency needs to be maintained. Preferred additives that can be used as component E) include antioxidants, heat stabilizers, UV stabilizers, gamma-ray stabilizers, hydrolysis stabilizers, antistatic agents, emulsifiers, nucleating agents, plasticizers, processing aids, impact modifiers, lubricants and / or release agents, flow aids or elastomer modifiers, chain extension additives, flame retardants different from components B) and C) and fillers and reinforcing agents or colorants different from component D). These additives can be used alone or in the form of a mixture / masterbatch. In the case of laser-transmitting products, the additives that can be used as component E) will be selected so that laser absorbers, such as especially carbon black, are not used. Laser absorbing additives are well known to those skilled in the art.

[0156] Heat stabilizers which can preferably be used as component E) are selected from the group consisting of sulfur-containing stabilizers, in particular sulfides, dialkylthiocarbamates or thiodipropionic acid; and heat stabilizers from the group of copper salts, in particular copper(I) iodide here, which is preferably used in combination with potassium iodide and / or sodium hypophosphite NaH2PO2; and sterically hindered amines, in particular tetramethylpiperidine derivatives, aromatic secondary amines, in particular diphenylamine, hydroquinone, substituted resorcinols, salicylates, benzotriazoles and benzophenones; and also sterically hindered phenols and aliphatic or aromatic substituted phosphites and variously substituted representatives of these groups.

[0157] The sterically hindered phenols are preferably those having at least one 3-tert-butyl-4-hydroxy-5-methylphenyl and / or at least one 3,5-di(tert-butyl-4-hydroxyphenyl) unit, wherein 1,6-hexanediol-bis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] [CAS No. 35074-77-2] ( 259, from BASF SE, Ludwigshafen, Germany), pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate][CAS No. 6683-19-8]( 1010, from BASF SE) and 3,9-bis[2-[3-(3-tert-butyl-4-hydroxy-5-methylphenyl)propionyloxy]-1,1-dimethylethyl]-2,4,8,10-tetraoxaspiro[5.5]undecane [CAS No. 90498-90-1] (ADK AO 80) is particularly preferred. ADK AO 80 is a commercially available product from Adeka-Palmerole SAS (Mulhouse, France).

[0158] Preferred among the aliphatic or aromatic substituted phosphites is bis(2,4-dicumylphenyl)pentaerythritol diphosphite [CAS No. 154862-43-8], which is marketed under the trade name S9228 is commercially available from Dover Chemical Corp. (Dover, USA), and tetrakis(2,4-di-tert-butylphenyl)-1,1-biphenyl-4,4'-diyl bisphosphonate [CAS No. 38613-77-3], which is, for example, P-EPQ is commercially available from Clariant International Ltd. (Muttenz, Switzerland).

[0159] Heat stabilizers which can be used as component E) are preferably used in amounts of 0.01 to 2 parts by mass, particularly preferably 0.05 to 1 part by mass, based in each case on 100 parts by mass of component A).

[0160] UV stabilizers which can be used as component E) preferably include substituted resorcinols, salicylates, benzotriazoles and benzophenones and HALS derivatives (hindered amine light stabilizers) which comprise at least one 2,2,6,6-tetramethyl-4-piperidinyl unit or benzophenone.

[0161] The UV stabilizers which can be used as component E) are preferably used in amounts of 0.01 to 2 parts by mass, particularly preferably 0.1 to 1 part by mass, based in each case on 100 parts by mass of component A).

[0162] The colorants used which can be used as component E) are preferably selected from inorganic pigments, in particular ultramarine blue, bismuth vanadate, iron oxide, titanium dioxide, zinc sulfide, tin titanium zinc oxide [CAS No. 923954-49-8], and organic dyes, preferably phthalocyanines, quinacridones, benzimidazoles, in particular Ni-2-hydroxy-naphthylbenzimidazole [CAS No. 42844-93-9] and / or pyrimidine-azo-benzimidazole [CAS No. 72102-84-2] and / or Pigment Yellow 192 [CAS No. 56279-27-7], and perylene, anthraquinone, in particular CI Solvent Yellow 163 [CAS No. 13676-91-0], wherein this list is not exhaustive and wherein the choice of the colorant is carried out in particular with regard to the requirements for laser transmission / laser absorption behavior.

[0163] In a specific embodiment, preferably in the case of laser absorbing components, the dyes used may also include carbon black and / or nigrosin.

[0164] Nucleating agents which can be used as component E) preferably include sodium or calcium phenylphosphinate, aluminum oxide or silicon dioxide, and very particularly preferably talc, this list being non-exhaustive.

[0165] The flow aid used which can be used as component E) preferably comprises a copolymer of at least one α-olefin and a methacrylate or acrylate of at least one aliphatic alcohol. Particular preference is given to copolymers in which the α-olefin comprises ethylene and / or propylene units and the methacrylate or acrylate comprises as alcohol component a linear or branched alkyl radical having 6 to 20 carbon atoms. 2-Ethylhexyl acrylate is very particularly preferred. Copolymers suitable as flow aids are distinguished not only by their composition, but also by their low molecular weight. Therefore, copolymers suitable for the composition according to the invention are first of all those which have an MFI of at least 100 g / 10 min, preferably at least 150 g / 10 min, particularly preferably at least 300 g / 10 min, when measured at 190° C. and a load of 2.16 kg. MFI, the melt flow index, is used to characterize the fluidity of thermoplastic melts and complies with ISO 1133 or ASTM D1238. As a flow aid, it is particularly preferred to use a copolymer of ethylene and 2-ethylhexyl acrylate having an MFI of 550, which is referred to as 37EH550.

[0166] As chain-extending additives and hydrolysis stabilizers which can be used as component E), preference is given to using bifunctional or polyfunctional branching or chain-extending additives which contain at least two branching or chain-extending functional groups per molecule. Branching or chain-extending additives are preferably low molecular weight oligomeric or polymeric compounds which have at least two chain-extending functional groups per molecule which are capable of reacting with alcohol groups and / or amide groups and / or carboxyl groups. Chain-extending functional groups are preferably isocyanates, carbodiimides, alcohols, epoxides, maleic anhydride, oxazolines, oxazines and oxazolones, with epoxides and carbodiimides being particularly preferred.

[0167] Particularly preferred difunctional or polyfunctional branching or chain-extending additives are diepoxides based on diglycidyl ethers (bisphenols and epichlorohydrin), based on aminoepoxy resins (aniline and epichlorohydrin), based on diglycidyl esters (cycloaliphatic dicarboxylic acids and epichlorohydrin), and also 2,2-bis[p-hydroxyphenyl]propane diglycidyl ether, bis[p-(N-methyl-N-2,3-epoxypropylamino)phenyl]methane, and epoxidized fatty acid esters of glycerol containing at least two epoxy groups per molecule, alone or in mixtures.

[0168] Particularly preferred difunctional or polyfunctional branching or chain-extending additives are glycidyl ethers, very particularly preferably bisphenol A diglycidyl ether [CAS No. 98460-24-3] or epoxidized fatty acid esters of glycerol, also very particularly preferably epoxidized soybean oil [CAS No. 8013-07-8] and / or epoxidized linseed oil [CAS No. 8016-11-3] and very particularly preferably carbodiimides, polymeric carbodiimides, such as, for example, poly-2,4,6-triisopropyl-1,3-dicarbodiimide and carbodiimides comprising pentaerythritol units, in particular 14,14′,15,15′-tetradehydro-7,7′-spirobi[dibenzo[b,g][1,9,4,6]dioxadiazacyclododecane] [CAS No. 1231148-36-9] being again particularly preferred among the carbodiimides.

[0169] Plasticizers which can preferably be used as component E) are dioctyl phthalate, dibenzyl phthalate, butyl benzyl phthalate, hydrocarbon oils or N-(n-butyl)benzenesulfonamide.

[0170] Preferred elastomer modifiers which can be used as component E) include in particular one or more graft polymers of:

[0171] E.1 5 to 95% by weight, preferably 30 to 90% by weight, of at least one ethylene monomer, and

[0172] E.2 95 to 5% by weight, preferably 70 to 10% by weight, of one or more grafted substrates having a glass transition temperature of <10° C., preferably <0° C., particularly preferably <−20° C., the weight percentages being based on 100% by weight of the elastomer modifier.

[0173] The graft base E.2 generally has an average particle size d50 value of 0.05 to 10 μm, preferably 0.1 to 5 μm, particularly preferably 0.2 to 1 μm, which is determinable by laser diffraction in accordance with ISO 13320.

[0174] The monomers according to E.1 are preferably mixtures of:

[0175] E.1.1 50 to 99% by weight of vinylaromatic compounds and / or ring-substituted vinylaromatic compounds, in particular styrene, α-methylstyrene, p-methylstyrene, p-chlorostyrene and / or (C1-C8)-alkyl methacrylates, in particular methyl methacrylate or ethyl methacrylate, and

[0176] E.1.2 1 to 50% by weight of vinyl cyanides, preferably unsaturated nitriles, in particular acrylonitrile and methacrylonitrile, and / or (meth)acrylic acid (C1-C8)-alkyl esters, in particular methyl methacrylate, glycidyl methacrylate, n-butyl acrylate, tert-butyl acrylate and / or derivatives, in particular anhydrides and imides of unsaturated carboxylic acids, in particular maleic anhydride or N-phenylmaleimide, wherein the percentages by weight of E.1.1 and E.1.2 are based on 100% by weight of elastomer modifier.

[0177] Preferred monomers E.1.1 are selected from at least one of the monomers styrene, α-methylstyrene and methyl methacrylate, and preferred monomers E.1.2 are selected from at least one of the monomers acrylonitrile, maleic anhydride, glycidyl methacrylate and methyl methacrylate. Particularly preferred monomers are E.1.1 styrene and E.1.2 acrylonitrile.

[0178] Suitable graft bases E.2 for graft polymers which can be used in the elastomer modifiers include, for example, diene rubbers, EPDM rubbers, ie those based on ethylene / propylene and optionally dienes, and acrylates, polyurethanes, silicones, chloroprene and ethylene / vinyl acetate rubbers. EPDM stands for ethylene-propylene-diene rubber.

[0179] Preferred graft substrates E.2 are diene rubbers, in particular diene rubbers based on butadiene, isoprene, etc., or mixtures of diene rubbers, or copolymers of diene rubbers or mixtures thereof with other copolymerizable monomers, in particular according to E.1.1 and E.1.2, provided that the glass transition temperature of component E.2 is <10°C, preferably <0°C, particularly preferably <-10°C.

[0180] Particularly preferred graft substrates E.2 are ABS polymers (emulsion, bulk and suspension ABS), where ABS stands for acrylonitrile-butadiene-styrene, as described, for example, in DE-A2 035 390 or in DE-A2 248 242 or in Ullmann, der Technischen Chemie, vol. 19 (1980), p. 277-295. The gel content of the graft base E.2 is preferably at least 30% by weight, particularly preferably at least 40% by weight (measured in toluene).

[0181] Elastomer modifiers / graft polymers which can be used as component E) are produced by free-radical polymerization, preferably by emulsion, suspension, solution or bulk polymerization, in particular by emulsion or bulk polymerization.

[0182] Particularly suitable graft rubbers also include ABS polymers which are produced according to US Pat. No. 4,937,285 by redox initiation with an initiator system consisting of an organic hydroperoxide and ascorbic acid.

[0183] As is known, since the grafting monomers do not necessarily have to be completely grafted onto the grafting substrate in the grafting reaction, the graft polymers according to the invention should also be understood to mean products produced by (co)polymerization of the grafting monomers in the presence of the grafting substrate and obtained together in the post-treatment.

[0184] Likewise, suitable acrylate rubbers are based on a graft base E.2, which is preferably a polymer of an alkyl acrylate, optionally with up to 40% by weight, based on E.2, of other polymerizable ethylenically unsaturated monomers. Preferred polymerizable acrylates include C1-C8-alkyl esters, preferably methyl, ethyl, butyl, n-octyl and 2-ethylhexyl esters; haloalkyl esters, preferably halo-C1-C8-alkyl esters, such as chloroethyl acrylate, glycidyl ester and mixtures of these monomers. Particular preference is given in this context to graft polymers having butyl acrylate as core and methyl methacrylate as shell, in particular EXL2300, Dow Corning Corporation, Midland, Michigan, USA.

[0185] Crosslinking can be achieved by copolymerization of monomers having more than one polymerizable double bond as an alternative to ethylenically unsaturated monomers. Preferred crosslinking monomers are esters of unsaturated monocarboxylic acids having 3 to 8 carbon atoms with unsaturated monohydric alcohols having 3 to 12 carbon atoms or with saturated polyols having 2 to 4 OH groups and 2 to 20 carbon atoms, preferably ethylene glycol dimethacrylate, allyl methacrylate; polyunsaturated heterocyclic compounds, preferably trivinyl cyanurate and triallyl cyanurate; polyfunctional vinyl compounds, preferably divinyl benzene and trivinyl benzene; and triallyl phosphates and diallyl phthalates.

[0186] Particularly preferred crosslinking monomers are allyl methacrylate, ethylene glycol dimethacrylate, diallyl phthalate and heterocyclic compounds having at least 3 ethylenically unsaturated groups.

[0187] Very particularly preferred crosslinking monomers are the cyclic monomers triallyl cyanurate, triallyl isocyanurate, triacryloylhexahydro-s-triazine, triallylbenzene. The amount of crosslinking monomers is preferably 0.02 to 5% by weight, in particular 0.05 to 2% by weight, based on the graft substrate E.2.

[0188] In the case of cyclic crosslinking monomers having at least 3 ethylenically unsaturated groups, it is advantageous to limit their amount to less than 1% by weight of the graft base E.2.

[0189] In addition to acrylates, preferred "other" polymerizable ethylenically unsaturated monomers which can optionally be used to produce the graft base E.2 are acrylonitrile, styrene, α-methylstyrene, acrylamide, vinyl C1-C6-alkyl ethers, methyl methacrylate, glycidyl methacrylate, butadiene. Preferred acrylate rubbers as graft base E.2 are emulsion polymers having a gel content of at least 60% by weight.

[0190] Further preferably suitable grafting substrates according to E.2 are silicone rubbers having grafting-active sites, as described in DE-A3 704 657, DE-A3 704 655, DE-A3 631 540 and DE-A3 631 539.

[0191] Preferred graft polymers containing silicone moieties are those containing methyl methacrylate or styrene-acrylonitrile as the shell and a silicone / acrylate graft as the core. Preferred styrene-acrylonitrile that can be used as the shell is SRK200. Methyl methacrylates preferably used as the shell include S2001 or S2030 or SX-005. It is particularly preferred to use S2001. The product name is Products of TRANSPAR® are available from Mitsubishi Rayon Co., Ltd. (Tokyo, Japan).

[0192] Crosslinking can be achieved by copolymerizing monomers having more than one polymerizable double bond. Preferred examples of crosslinking monomers are esters of unsaturated monocarboxylic acids having 3 to 8 carbon atoms with unsaturated monohydric alcohols having 3 to 12 carbon atoms, or with saturated polyols having 2 to 4 OH groups and 2 to 20 carbon atoms, preferably ethylene glycol dimethacrylate, allyl methacrylate; polyunsaturated heterocyclic compounds, preferably trivinyl cyanurate and triallyl cyanurate; polyfunctional vinyl compounds, preferably divinyl benzene and trivinyl benzene; triallyl phosphate and diallyl phthalate are also included.

[0193] Preferred crosslinking monomers are allyl methacrylate, ethylene glycol dimethacrylate, diallyl phthalate and heterocyclic compounds having at least 3 ethylenically unsaturated groups.

[0194] Particularly preferred crosslinking monomers are the cyclic monomers triallyl cyanurate, triallyl isocyanurate, triacryloylhexahydro-s-triazine, triallylbenzene. The amount of crosslinking monomers is preferably 0.02 to 5% by weight, in particular 0.05 to 2% by weight, based on the graft substrate E.2.

[0195] In the case of cyclic crosslinking monomers having at least 3 ethylenically unsaturated groups, it is advantageous to limit their amount to less than 1% by weight of the graft base E.2.

[0196] In addition to acrylates, preferred "other" polymerizable ethylenically unsaturated monomers which can optionally be used to produce the graft base E.2 are acrylonitrile, styrene, α-methylstyrene, acrylamide, vinyl C1-C6-alkyl ethers, methyl methacrylate, glycidyl methacrylate, butadiene. Preferred acrylate rubbers as graft base E.2 are emulsion polymers having a gel content of at least 60% by weight.

[0197] In addition to elastomer modifiers based on graft polymers, further materials which can likewise be used are elastomer modifiers which are not based on graft polymers and have a glass transition temperature of <10° C., preferably <0° C., particularly preferably <−20° C. These preferably include elastomers having a block copolymer structure and further thermoplastic fusible elastomers, in particular EPM, EPDM and / or SEBS rubbers (EPM=ethylene-propylene copolymers, EPDM=ethylene-propylene-diene rubber and SEBS=styrene-ethylene-butylene-styrene copolymers).

[0198] Lubricants and mold release agents which can be used as component E) are preferably selected from the group consisting of long-chain fatty acids, salts of long-chain fatty acids, ester derivatives of long-chain fatty acids and montan wax.

[0199] Preferred long-chain fatty acids are stearic acid or behenic acid. Preferred salts of long-chain fatty acids are calcium stearate, magnesium stearate, aluminum stearate or zinc stearate. Preferred ester derivatives of long-chain fatty acids are those based on pentaerythritol, specifically C 16 -C 18 Fatty acid esters [CAS No.68604-44-4] or [CAS No.85116-93-4].

[0200] In the context of the present invention, montan wax is a mixture of linear saturated carboxylic acids with a chain length of 28 to 32 carbon atoms. According to the invention, particular preference is given to using lubricants and / or mold release agents from the group consisting of esters of saturated or unsaturated aliphatic carboxylic acids with 8 to 40 carbon atoms and aliphatic saturated alcohols with 2 to 40 carbon atoms and metal salts of saturated or unsaturated aliphatic carboxylic acids with 8 to 40 carbon atoms, among which pentaerythritol tetrastearate, calcium stearate [CAS No. 1592-23-0] and / or ethylene glycol dimontanate, in particular here from Clariant, Muttenz, Basle E [CAS No. 74388-22-0] is very particularly preferred and, for example, as P861 pentaerythritol tetrastearate [CAS No. 115-83-3] available from Emery Oleochemicals GmbH (Düsseldorf, Germany) is very particularly preferred.

[0201] Further flame retardants which can preferably be used as component E) are mineral flame retardants, nitrogen-containing flame retardants or phosphorus-containing flame retardants which are different from components B) and C).

[0202] In an alternative embodiment, if desired and taking into account the disadvantages of loss of laser transparency, it is also possible to use flame retardants (as laser absorbers) which have an adverse effect on the laser transmittance of products based on the polymer composition according to the invention.

[0203] Among the mineral flame retardants, magnesium hydroxide is particularly preferred.

[0204] In an alternative embodiment, however, if desired, it is also possible to use nitrogen-containing flame retardants and flame retardant synergists as flame retardants for component E). Preferred nitrogen-containing flame retardants that can be used as component E) are reaction products of trichlorotriazine, piperazine and morpholine according to CAS No. 1078142-02-5, in particular MCA PPM Triazin HF (MCAPPM Triazine HF Salt) from MCA Technologies GmbH (Biel-Benken, Switzerland), and condensation products of melamine cyanurate or melamine, in particular melem, melam, cyanuric acid diamine (Melon) or higher condensation compounds of this type. Preferred inorganic nitrogen-containing compounds are ammonium salts.

[0205] It is further possible to use salts of aliphatic and aromatic sulfonic acids and mineral flame retardant additives, in particular aluminum hydroxide or Ca Mg carbonate hydrate (DE-A 4 236 122), as flame retardants for component E).

[0206] Flame retardant synergists from the group of oxygen-containing, nitrogen-containing or sulfur-containing metal compounds are also suitable as flame retardants for component E). Preference is given to zinc-free compounds, in particular molybdenum oxide, magnesium oxide, magnesium carbonate, calcium carbonate, calcium oxide, titanium nitride, magnesium nitride, calcium phosphate, calcium borate, magnesium borate, or mixtures thereof, with calcium carbonate being very particularly preferred. Calcium carbonate which can preferably be used has an average particle size (d50) in the range of 0.5 μm to 10 μm, determinable by laser diffraction according to ISO 13320, with a d50 in the range of 0.7 μm to 5 μm being preferred and a d50 in the range of 1.0 μm to 3 μm being particularly preferred. A measuring instrument suitable for determining the d50 of calcium carbonate is, for example, the TEM® from Malvern Panalytical GmbH (Kassel, Germany). 2000.

[0207] In an alternative embodiment, however, if desired, zinc-containing compounds can also be used as flame retardants for component E). These preferably include zinc oxide, zinc borate, zinc stannate, zinc hydroxystannate, zinc sulfide and zinc nitride, or mixtures thereof.

[0208] In an alternative embodiment, however, if desired, it is also possible to use calcium stannate or calcium hydroxystannate as flame retardant for component E).

[0209] However, the flame retardants used which are different from components B) and C) and which can be used as component E) preferably also include phosphonic acids Inorganic aluminum salt. According to Wikipedia (http: / / de.wikipedia.org / wiki / Phosphons%C3%A4ure), phosphonic acid is understood to mean a substance with the empirical formula H3PO3 [CAS No.13598-36-2]. The salts of phosphonic acid are called phosphonates. Phosphonic acid can exist in two tautomeric forms, one of which has a free electron pair on the phosphorus atom and the other has an oxygen doubly bonded to the phosphorus (P=O). The tautomeric equilibrium is completely in favor of the form with the double-bonded oxygen. According to AF Holleman, E. Wiberg: Lehrbuch der Anorganischen Chemie. 101st edition Walter de Gruyter, Berlin / New York 1995, ISBN 3-11-012641-9, p.764, the term "phosphorous acid (Phosphorige ")" and "phosphite" should only be used for tautomeric substances having a free electron pair at phosphorus. However, the terms "phosphorous acid" and "phosphite" have previously also been used for tautomeric forms having oxygen double-bonded to phosphorus, and therefore, in the present invention, the terms "phosphonic acid" and "phosphorous acid" as well as the terms "phosphonate" and "phosphite" are used synonymously with each other.

[0210] Preferred aluminum salts of phosphonic acid are one or more selected from the following groups:

[0211] Primary aluminum phosphonate [Al(H2PO3)3],

[0212] Basic aluminum phosphonate [Al(OH)H2PO3)2·2H2O],

[0213] Al2(HPO3)3·xAl2O3·nH2O, wherein x is in the range of 2.27 to 1 and n is in the range of 0 to 4,

[0214] Al2(HPO3)3·(H2O) of formula (V) q , wherein q is 0, 1, 2, 3 or 4, specifically aluminum phosphonate tetrahydrate [Al2(HPO3)3·4H2O] or secondary aluminum phosphonate [Al2(HPO3)3],

[0215] Al2M of formula (VI) z (HPO3) y (OH) v ·(H2O) w , wherein M represents an alkali metal ion and z is in the range of 0.01 to 1.5, y is in the range of 2.63 to 3.5, v is in the range of 0 to 2 and w is in the range of 0 to 4, and

[0216] Al2(HPO3) of formula (VII) u (H2PO3) t ·(H2O) s , where u is in the range of 2 to 2.99, t is in the range of 2 to 0.01, and s is in the range of 0 to 4,

[0217] In the formula (VI), z, y and v and in the formula (VII) u and t may only have such numbers that the corresponding aluminum salt of the phosphonic acid is uncharged overall.

[0218] Preferred alkali metals M in formula (VI) are sodium and potassium.

[0219] Particularly preferred aluminum salts of phosphonic acid are selected from the following group:

[0220] Primary aluminum phosphonate [Al(H2PO3)3],

[0221] Secondary aluminum phosphonate [Al2(HPO3)3],

[0222] Basic aluminum phosphonate [Al(OH)H2PO3)2·2H2O],

[0223] Aluminum phosphonate tetrahydrate [Al2(HPO3)3·4H2O] and

[0224] Al2(HPO3)3·xAl2O3·nH2O, wherein x is in the range of 2.27 to 1 and n is in the range of 0 to 4.

[0225] Secondary aluminum phosphonate [Al2(HPO3)3], [CAS No. 71449-76-8] and secondary aluminum phosphonate tetrahydrate [Al2(HPO3)3.4H2O], [CAS No. 156024-71-4] are very particularly preferred, and secondary aluminum phosphonate [Al2(HPO3)3] is especially preferred.

[0226] Preferred other phosphorus-containing flame retardants other than components B) and C) also include other organic metal phosphinates (Metallphosphinate), red phosphorus, inorganic metal hypophosphites (Metallhypophosphites), other metal phosphonates, derivatives of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO derivatives), resorcinol bis(diphenyl phosphate) (RDP) (including oligomers), bisphenol A bis(diphenyl phosphate) (BDP) (including oligomers), melamine pyrophosphate, melamine polyphosphate, melamine poly(aluminum phosphate), melamine poly(zinc phosphate) or phenoxyphosphazene oligomers, and mixtures thereof.

[0227] Further flame retardants which can be used as component E) are char formers, particularly preferably phenolic resins, polycarbonates, polyimides, polysulfones, polyethersulfones or polyetherketones, and anti-drip agents, in particular tetrafluoroethylene polymers.

[0228] The flame retardants which can be used as component E) can be added in pure form and via masterbatches or briquettes.

[0229] However, in alternative embodiments, if necessary and taking into account the disadvantages of the loss of halogen-free properties of the flame retardant in particular, halogen-containing flame retardants can also be used. Preferred halogen-containing flame retardants are commercially available organic halogen compounds, particularly preferably ethylene-1,2-bistetrabromophthalimide, decabromodiphenylethane, tetrabromobisphenol A epoxy oligomers, tetrabromobisphenol A oligocarbonates, tetrachlorobisphenol A oligocarbonates, polypentabromobenzyl acrylate, brominated polystyrene or brominated polyphenylene ether, which can be used alone or in combination with a synergist, the synergist is especially antimony trioxide or antimony pentoxide (if the disadvantages of laser transmittance have been taken into account, when required for specific uses), wherein among the halogen-containing flame retardants, tetrabromobisphenol A epoxy oligomers and tetrabromobisphenol A oligocarbonates are particularly preferred.

[0230] In alternative embodiments, other fillers and reinforcing agents than component D) can also be used, if required for the specific application and optionally taking into account disadvantages in laser transmittance.

[0231] These are preferably selected from one or more fillers and / or reinforcing agents from the group consisting of carbon fibers [CAS No. 7440-44-0], calcium silicate [CAS No. 1344-95-2], calcium metasilicate [CAS No. 10101-39-0], magnesium carbonate [CAS No. 546-93-0], kaolin [CAS No. 1332-58-7], calcined kaolin [CAS No. 92704-41-1], chalk [CAS No. 1317-65-3], kyanite [CAS No. 1302-76-7], powdered or ground quartz [CAS No. 14808-60-7], mica [CAS No. 1318-94-1], phlogopite [CAS No. 12251-00-2], feldspar [CAS No. 68476-25-5], wollastonite [CAS No. 13983-17-0], montmorillonite [CAS No. 67479-91-8], pseudoboehmite of formula AlO(OH), magnesium carbonate [CAS No. 12125-28-9] and talc [CAS No. 14807-96-6], and, if desired, barium sulfate [CAS No. 7727-43-7].

[0232] Among the fibrous fillers or reinforcing agents other than component D), wollastonite is particularly preferred. In the case of laser-absorbing components / products, carbon fibers can also be used as reinforcing material.

[0233] In the case of laser absorbing components, at least one laser absorber selected from the group consisting of antimony trioxide, tin oxide, tin orthophosphate, barium titanate, aluminum oxide, copper hydroxyphosphate, copper orthophosphate, potassium copper diphosphate, copper hydroxide, antimony tin oxide, bismuth trioxide and anthraquinone can be used as component E) without losing the high laser transmittance property. Tin oxide, antimony trioxide or antimony tin oxide are particularly preferred. Antimony trioxide is very particularly preferred.

[0234] Laser absorbers, especially antimony trioxide, can be used directly as powder or in the form of masterbatches. Preferred masterbatches are those based on polyamides and / or polyolefins, preferably polyethylene. Antimony trioxide is very particularly preferably used in the form of masterbatches based on polyamide 6.

[0235] The laser absorbent may be used alone or as a mixture of two or more laser absorbents.

[0236] Laser absorbers can absorb laser light of a specific wavelength. In practice, this wavelength is in the range of 157 nm to 10.6 μm. Examples of lasers of these wavelengths are described in WO 2009 / 003976 A1. Nd:YAG lasers and CO2 lasers that can achieve wavelengths of 1064, 532, 355 and 266 nm are preferably used.

[0237] Other preferred uses

[0238] The present invention preferably relates to the use of the following compounds:

[0239] B) Aluminum salt of general formula (I)

[0240]

[0241] Where R represents C1-C 12 - alkyl, preferably representing methyl, ethyl, isopropyl or isobutyl, tert-butyl or n-butyl, particularly preferably representing ethyl or methyl, very particularly preferably representing methyl, to achieve a CTI A of 600 according to IEC 60112-2010 in or for a polyester-based product, wherein per 100 parts by mass of polyalkylene terephthalates or polycycloalkylene terephthalates, in particular polybutylene terephthalate, polyethylene terephthalate or poly-1,4-cyclohexanedimethanol terephthalate, 1 to 80 parts by mass, preferably 2 to 60 parts by mass, particularly preferably 3 to 30 parts by mass and especially preferably 5 to 20 parts by mass of an aluminium salt of the formula (I) are used,

[0242] The present invention particularly preferably relates to the use of B) aluminum methylphosphonate of the formula (Ia):

[0243]

[0244] In order to achieve a CTI A of 600 according to IEC 60112-2010 in or for polyester-based products, 1 to 80 parts by mass, preferably 2 to 60 parts by mass, particularly preferably 3 to 30 parts by mass, and especially preferably 5 to 20 parts by mass of the aluminum salt of the formula (Ia) are used per 100 parts by mass of polyalkylene terephthalates or polycycloalkylene terephthalates, in particular polybutylene terephthalate, polyethylene terephthalate or poly-1,4-cyclohexanedimethanol terephthalate.

[0245] The present invention preferably relates to the use of B) aluminum salts of the general formula (I):

[0246]

[0247] Where R represents C1-C 12 - alkyl, preferably representing methyl, ethyl, isopropyl or isobutyl, tert-butyl or n-butyl, particularly preferably representing ethyl or methyl, very particularly preferably representing methyl, to achieve a CTI A of 600 according to IEC 60112-2010 in polyester-based products, wherein per 100 parts by mass of polyalkylene terephthalates or polycycloalkylene terephthalates, in particular polybutylene terephthalate, polyethylene terephthalate or poly-1,4-cyclohexanedimethanol terephthalate, 1 to 80 parts by mass, preferably 2 to 60 parts by mass, particularly preferably 3 to 30 parts by mass and especially preferably 5 to 20 parts by mass of the aluminum salt of the formula (I),

[0248] as well as

[0249] 5 to 120 parts by mass, preferably 7 to 80 parts by mass, particularly preferably 8 to 60 parts by mass, especially preferably 10 to 50 parts by mass of at least one organic phosphinate of the formula (II) and / or at least one diphosphinate of the formula (III) and / or polymers thereof which may be used as component C),

[0250]

[0251] in

[0252] R 1 , R 2 are identical or different and represent a linear or branched C1-C6-alkyl group and / or represent a C6-C 14 - aryl,

[0253] R 3 Represents linear or branched C1-C 10 -alkylene, C6-C 10-arylene or C1-C6-alkyl-C6-C 10 -Arylene or C6-C 10 - aryl-C1-C6-alkylene,

[0254] M stands for aluminum, zinc or titanium,

[0255] m represents an integer from 1 to 4,

[0256] n represents an integer from 1 to 3,

[0257] x represents 1 and 2,

[0258] In the formula (III), n, x and m can simultaneously only be integers such that the diphosphite of the formula (III) as a whole is uncharged, provided that component B) is used in a lower mass fraction than component C).

[0259] The present invention particularly preferably relates to the use of the following compounds:

[0260] B) Aluminum methylphosphonate of formula (Ia)

[0261]

[0262] to a CTI A of 600 according to IEC 60112-2010 in or for a polyester-based product, wherein per 100 parts by mass of polyalkylene terephthalates or polycycloalkylene terephthalates, in particular polybutylene terephthalate, polyethylene terephthalate or poly-1,4-cyclohexanedimethanol terephthalate, 1 to 800 parts by mass, preferably 2 to 60 parts by mass, particularly preferably 3 to 30 parts by mass, and especially preferably 5 to 20 parts by mass of an aluminum salt of the formula (Ia) are used,

[0263] as well as

[0264] 5 to 120 parts by mass, preferably 7 to 80 parts by mass, particularly preferably 8 to 60 parts by mass, especially preferably 10 to 50 parts by mass of at least one organic phosphinate of the formula (II) and / or at least one diphosphinate of the formula (III) and / or polymers thereof which may be used as component C),

[0265]

[0266] in

[0267] R 1 , R 2 are identical or different and represent a linear or branched C1-C6-alkyl group and / or represent a C6-C 14 - aryl,

[0268] R3 Represents linear or branched C1-C 10 -alkylene, C6-C 10 -arylene or C1-C6-alkyl-C6-C 10 -Arylene or C6-C 10 - aryl-C1-C6-alkylene,

[0269] M stands for aluminum, zinc or titanium,

[0270] m represents an integer from 1 to 4,

[0271] n represents an integer from 1 to 3,

[0272] x represents 1 and 2,

[0273] In the formula (III), n, x and m can simultaneously only be integers such that the diphosphite of the formula (III) as a whole is uncharged, provided that component B) is used in a lower mass fraction than component C).

[0274] The present invention particularly preferably relates to the use of the following compounds:

[0275] B) Aluminum methylphosphonate of formula (Ia)

[0276]

[0277] to achieve a CTI A of 600 according to IEC 60112-2010 in or for a polyester-based product, wherein per 100 parts by mass of polyalkylene terephthalates or polycycloalkylene terephthalates, in particular polybutylene terephthalate, polyethylene terephthalate or poly-1,4-cyclohexanedimethanol terephthalate, 1 to 80 parts by mass, preferably 2 to 60 parts by mass, particularly preferably 3 to 30 parts by mass, and especially preferably 5 to 20 parts by mass of an aluminum salt of the formula (Ia) are used,

[0278] as well as

[0279] 5 to 120 parts by mass, preferably 7 to 80 parts by mass, particularly preferably 8 to 60 parts by mass, and especially preferably 10 to 50 parts by mass of aluminum tris(diethylphosphinate), provided that component B) is used in a lower mass fraction than component C).

[0280] The present invention preferably relates to the use of the following compounds:

[0281] B) Aluminum salt of general formula (I)

[0282]

[0283] Where R represents C1-C 12-alkyl, preferably representing methyl, ethyl, isopropyl or isobutyl, tert-butyl or n-butyl, particularly preferably representing ethyl or methyl, very particularly preferably representing methyl, to achieve a CTI A of 600 according to IEC 60112-2010 in or for a polyester-based product, wherein per 100 parts by mass of polyalkylene terephthalates or polycycloalkylene terephthalates, in particular polybutylene terephthalate, polyethylene terephthalate or poly-1,4-cyclohexanedimethanol terephthalate, 1 to 80 parts by mass, preferably 2 to 60 parts by mass, particularly preferably 3 to 30 parts by mass and especially preferably 5 to 20 parts by mass of an aluminium salt of the formula (I) are used,

[0284] as well as

[0285] 5 to 120 parts by mass, preferably 7 to 80 parts by mass, particularly preferably 8 to 60 parts by mass, especially preferably 10 to 50 parts by mass of at least one organic phosphinate of the formula (II) and / or at least one diphosphinate of the formula (III) and / or polymers thereof which may be used as component C),

[0286]

[0287] in

[0288] R 1 , R 2 are identical or different and represent a linear or branched C1-C6-alkyl group and / or represent a C6-C 14 - aryl,

[0289] R 3 Represents linear or branched C1-C 10 -alkylene, C6-C 10 -arylene or C1-C6-alkyl-C6-C 10 -Arylene or C6-C 10 - aryl-C1-C6-alkylene,

[0290] M stands for aluminum, zinc or titanium,

[0291] m represents an integer from 1 to 4,

[0292] n represents an integer from 1 to 3,

[0293] x represents 1 and 2,

[0294] wherein n, x and m in formula (III) can simultaneously only be integers, so that the diphosphite of formula (III) as a whole is uncharged,

[0295] as well as

[0296] 3 to 300 parts by mass, preferably 5 to 200 parts by mass, particularly preferably 10 to 120 parts by mass and especially preferably 15 to 90 parts by mass of at least one glass-based filler and / or reinforcing agent which can be used as component D), with the proviso that component B) is used in a lower mass fraction than component C).

[0297] The present invention particularly preferably relates to the use of the following compounds:

[0298] B) Aluminum methylphosphonate of formula (Ia)

[0299]

[0300] to achieve a CTI A of 600 according to IEC 60112-2010 in or for a polyester-based product, wherein per 100 parts by mass of polyalkylene terephthalates or polycycloalkylene terephthalates, in particular polybutylene terephthalate, polyethylene terephthalate or poly-1,4-cyclohexanedimethanol terephthalate, 1 to 80 parts by mass, preferably 2 to 60 parts by mass, particularly preferably 3 to 30 parts by mass, and especially preferably 5 to 20 parts by mass of an aluminum salt of the formula (Ia) are used,

[0301] 5 to 120 parts by mass, preferably 7 to 80 parts by mass, particularly preferably 8 to 60 parts by mass, especially preferably 10 to 50 parts by mass of at least one organic phosphinate of the formula (II) and / or at least one diphosphinate of the formula (III) and / or polymers thereof which may be used as component C),

[0302]

[0303] in

[0304] R 1 , R 2 are identical or different and represent a linear or branched C1-C6-alkyl group and / or represent a C6-C 14 - aryl,

[0305] R 3 Represents linear or branched C1-C 10 -alkylene, C6-C 10 -arylene or C1-C6-alkyl-C6-C 10 -Arylene or C6-C 10 - aryl-C1-C6-alkylene,

[0306] M stands for aluminum, zinc or titanium,

[0307] m represents an integer from 1 to 4,

[0308] n represents an integer from 1 to 3,

[0309] x represents 1 and 2,

[0310] wherein n, x and m in formula (III) can simultaneously only be integers, so that the diphosphite of formula (III) as a whole is uncharged,

[0311] as well as

[0312] 3 to 300 parts by mass, preferably 5 to 200 parts by mass, particularly preferably 10 to 120 parts by mass and especially preferably 15 to 90 parts by mass of at least one glass-based filler and / or reinforcing agent which can be used as component D), with the proviso that component B) is used in a lower mass fraction than component C).

[0313] The present invention particularly preferably relates to the use of the following compounds:

[0314] B) Aluminum methylphosphonate of formula (Ia)

[0315]

[0316] to achieve a CTI A of 600 according to IEC 60112-2010 in or for a polyester-based product, wherein per 100 parts by mass of polyalkylene terephthalates or polycycloalkylene terephthalates, in particular polybutylene terephthalate, polyethylene terephthalate or poly-1,4-cyclohexanedimethanol terephthalate, 1 to 80 parts by mass, preferably 2 to 60 parts by mass, particularly preferably 3 to 30 parts by mass, and especially preferably 5 to 20 parts by mass of an aluminum salt of the formula (Ia) are used,

[0317] 5 to 120 parts by mass, preferably 7 to 80 parts by mass, particularly preferably 8 to 60 parts by mass, especially preferably 10 to 50 parts by mass of at least one organic phosphinate of the formula (II) and / or at least one diphosphinate of the formula (III) and / or polymers thereof which may be used as component C),

[0318]

[0319] in

[0320] R 1 , R 2 are identical or different and represent a linear or branched C1-C6-alkyl group and / or represent a C6-C 14 - aryl,

[0321] R 3 Represents linear or branched C1-C 10 -alkylene, C6-C 10 -arylene or C1-C6-alkyl-C6-C10 -Arylene or C6-C 10 - aryl-C1-C6-alkylene,

[0322] M stands for aluminum, zinc or titanium,

[0323] m represents an integer from 1 to 4,

[0324] n represents an integer from 1 to 3,

[0325] x represents 1 and 2,

[0326] wherein n, x and m in formula (III) can simultaneously only be integers, so that the diphosphite of formula (III) as a whole is uncharged,

[0327] as well as

[0328] 3 to 300 parts by mass, preferably 5 to 200 parts by mass, particularly preferably 10 to 120 parts by mass, and especially preferably 15 to 90 parts by mass of glass fibers can be used as component D), provided that component B) is used in a lower mass fraction than component C).

[0329] The present invention particularly preferably relates to the use of the following compounds:

[0330] B) Aluminum methylphosphonate of formula (Ia)

[0331]

[0332] to achieve a CTI A of 600 according to IEC 60112-2010 in or for a polyester-based product, wherein per 100 parts by mass of polyalkylene terephthalates or polycycloalkylene terephthalates, in particular polybutylene terephthalate, polyethylene terephthalate or poly-1,4-cyclohexanedimethanol terephthalate, 1 to 80 parts by mass, preferably 2 to 60 parts by mass, particularly preferably 3 to 30 parts by mass, and especially preferably 5 to 20 parts by mass of an aluminum salt of the formula (Ia) are used,

[0333] 5 to 120 parts by mass, preferably 7 to 80 parts by mass, particularly preferably 8 to 60 parts by mass, and especially preferably 10 to 50 parts by mass of aluminum tris(diethylphosphinate) as component C)

[0334] as well as

[0335] 3 to 300 parts by mass, preferably 5 to 200 parts by mass, particularly preferably 10 to 120 parts by mass and especially preferably 15 to 90 parts by mass of at least one glass-based filler and / or reinforcing agent which can be used as component D), with the proviso that component B) is used in a lower mass fraction than component C).

[0336] The present invention particularly preferably relates to the use of the following compounds:

[0337] B) Aluminum methylphosphonate of formula (Ia)

[0338]

[0339] to achieve a CTI A of 600 according to IEC 60112-2010 in or for a polyester-based product, wherein per 100 parts by mass of polyalkylene terephthalates or polycycloalkylene terephthalates, in particular polybutylene terephthalate, polyethylene terephthalate or poly-1,4-cyclohexanedimethanol terephthalate, 1 to 80 parts by mass, preferably 2 to 60 parts by mass, particularly preferably 3 to 30 parts by mass, and especially preferably 5 to 20 parts by mass of an aluminum salt of the formula (Ia) are used,

[0340] 5 to 120 parts by mass, preferably 7 to 80 parts by mass, particularly preferably 8 to 60 parts by mass, and especially preferably 10 to 50 parts by mass of aluminum tris(diethylphosphinate) as component C)

[0341] as well as

[0342] 3 to 300 parts by mass, preferably 5 to 200 parts by mass, particularly preferably 10 to 120 parts by mass, and especially preferably 15 to 90 parts by mass of glass fibers can be used as component D), provided that component B) is used in a lower mass fraction than component C).

[0343] The present invention preferably relates to the use of the following compounds:

[0344] B) Aluminum salt of general formula (I)

[0345]

[0346] Where R represents C1-C 12-alkyl, preferably represents methyl, ethyl, isopropyl or isobutyl, tert-butyl or n-butyl, particularly preferably represents ethyl or methyl, very particularly preferably represents methyl, in order to achieve, in a polyester-based product or for such product, a CTI A of 600 according to IEC 60112-2010 and a laser transmittance of at least 8% determinable according to DVS guideline 2243 (01 / 2014) at a wall thickness of 1.5 mm, wherein per 100 parts by mass of polyalkylene terephthalates or polycycloalkylene terephthalates, in particular polybutylene terephthalate, polyethylene terephthalate or poly-1,4-cyclohexanedimethanol terephthalate, 1 to 80 parts by mass, preferably 2 to 60 parts by mass, particularly preferably 3 to 30 parts by mass and especially preferably 5 to 20 parts by mass of the aluminum salt of the formula (I) are used.

[0347] The present invention particularly preferably relates to the use of the following compounds:

[0348] B) Aluminum methylphosphonate of formula (Ia)

[0349]

[0350] 1 to 80 parts by mass, preferably 2 to 60 parts by mass, particularly preferably 3 to 30 parts by mass, particularly preferably 5 to 20 parts by mass, of the aluminum salt of the formula (Ia) are used per 100 parts by mass of polyalkylene terephthalates or polycycloalkylene terephthalates, in particular polybutylene terephthalate, polyethylene terephthalate or poly-1,4-cyclohexanedimethanol terephthalate, in order to achieve in or for a polyester-based product at a wall thickness of 1.5 mm a CTI A of 600 according to IEC 60112-2010 and a laser transmittance of at least 8% determinable according to DVS guideline 2243 (01 / 2014).

[0351] The present invention preferably relates to the use of the following compounds:

[0352] B) Aluminum salt of general formula (I)

[0353]

[0354] Where R represents C1-C 12- alkyl, preferably representing methyl, ethyl, isopropyl or isobutyl, tert-butyl or n-butyl, particularly preferably representing ethyl or methyl, very particularly preferably representing methyl, to achieve in or for a polyester-based product at a wall thickness of 1.5 mm a CTI A of 600 according to IEC 60112-2010 and a laser transmittance determinable according to DVS guideline 2243 (01 / 2014) of at least 8%, wherein per 100 parts by mass of polyalkylene terephthalates or polycycloalkylene terephthalates, in particular polybutylene terephthalate, polyethylene terephthalate or poly-1,4-cyclohexanedimethanol terephthalate, 1 to 80 parts by mass, preferably 2 to 60 parts by mass, particularly preferably 3 to 30 parts by mass and especially preferably 5 to 20 parts by mass of an aluminium salt of the formula (I),

[0355] as well as

[0356] 5 to 120 parts by mass, preferably 7 to 80 parts by mass, particularly preferably 8 to 60 parts by mass, especially preferably 10 to 50 parts by mass of at least one organic phosphinate of the formula (II) and / or at least one diphosphinate of the formula (III) and / or polymers thereof which may be used as component C),

[0357]

[0358] in

[0359] R 1 , R 2 are identical or different and represent a linear or branched C1-C6-alkyl group and / or represent a C6-C 14 - aryl,

[0360] R 3 Represents linear or branched C1-C 10 -alkylene, C6-C 10 -arylene or C1-C6-alkyl-C6-C 10 -Arylene or C6-C 10 - aryl-C1-C6-alkylene,

[0361] M stands for aluminum, zinc or titanium,

[0362] m represents an integer from 1 to 4,

[0363] n represents an integer from 1 to 3,

[0364] x represents 1 and 2,

[0365] In the formula (III), n, x and m can simultaneously only be integers such that the diphosphite of the formula (III) as a whole is uncharged, provided that component B) is used in a lower mass fraction than component C).

[0366] The present invention particularly preferably relates to the use of the following compounds:

[0367] B) Aluminum methylphosphonate of formula (Ia)

[0368]

[0369] to achieve in or for a polyester-based product a CTI A of 600 according to IEC 60112-2010 and a laser transmittance of at least 8% determinable according to DVS Guideline 2243 (01 / 2014) at a wall thickness of 1.5 mm, wherein per 100 parts by mass of polyalkylene terephthalates or polycycloalkylene terephthalates, in particular polybutylene terephthalate, polyethylene terephthalate or poly-1,4-cyclohexanedimethanol terephthalate, 1 to 80 parts by mass, preferably 2 to 60 parts by mass, particularly preferably 3 to 30 parts by mass and especially preferably 5 to 20 parts by mass of an aluminum salt of the formula (Ia),

[0370] as well as

[0371] 5 to 120 parts by mass, preferably 7 to 80 parts by mass, particularly preferably 8 to 60 parts by mass, especially preferably 10 to 50 parts by mass of at least one organic phosphinate of the formula (II) and / or at least one diphosphinate of the formula (III) and / or polymers thereof which may be used as component C),

[0372]

[0373] in

[0374] R 1 , R 2 are identical or different and represent a linear or branched C1-C6-alkyl group and / or represent a C6-C 14 - aryl,

[0375] R 3 Represents linear or branched C1-C 10 -alkylene, C6-C 10 -arylene or C1-C6-alkyl-C6-C 10 -Arylene or C6-C 10 - aryl-C1-C6-alkylene,

[0376] M stands for aluminum, zinc or titanium,

[0377] m represents an integer from 1 to 4,

[0378] n represents an integer from 1 to 3,

[0379] x represents 1 and 2,

[0380] In the formula (III), n, x and m can simultaneously only be integers such that the diphosphite of the formula (III) as a whole is uncharged, provided that component B) is used in a lower mass fraction than component C).

[0381] The present invention preferably relates to the use of the following compounds:

[0382] B) Aluminum salt of formula (I)

[0383]

[0384] Where R represents C1-C 12 - alkyl, preferably representing methyl, ethyl, isopropyl or isobutyl, tert-butyl or n-butyl, particularly preferably representing ethyl or methyl, very particularly preferably representing methyl, to achieve in or for a polyester-based product at a wall thickness of 1.5 mm a CTI A of 600 according to IEC 60112-2010 and a laser transmittance determinable according to DVS guideline 2243 (01 / 2014) of at least 8%, wherein per 100 parts by mass of polyalkylene terephthalates or polycycloalkylene terephthalates, in particular polybutylene terephthalate, polyethylene terephthalate or poly-1,4-cyclohexanedimethanol terephthalate, 1 to 80 parts by mass, preferably 2 to 60 parts by mass, particularly preferably 3 to 30 parts by mass and especially preferably 5 to 20 parts by mass of an aluminium salt of the formula (I),

[0385] 5 to 120 parts by mass, preferably 7 to 80 parts by mass, particularly preferably 8 to 60 parts by mass, especially preferably 10 to 50 parts by mass of at least one organic phosphinate of the formula (II) and / or at least one diphosphinate of the formula (III) and / or polymers thereof which may be used as component C),

[0386]

[0387] in

[0388] R 1 , R 2 are identical or different and represent a linear or branched C1-C6-alkyl group and / or represent a C6-C 14 - aryl,

[0389] R 3 Represents linear or branched C1-C 10 -alkylene, C6-C10 -arylene or C1-C6-alkyl-C6-C 10 -Arylene or C6-C 10 - aryl-C1-C6-alkylene,

[0390] M stands for aluminum, zinc or titanium,

[0391] m represents an integer from 1 to 4,

[0392] n represents an integer from 1 to 3,

[0393] x represents 1 and 2,

[0394] wherein n, x and m in formula (III) can simultaneously only be integers, so that the diphosphite of formula (III) as a whole is uncharged,

[0395] as well as

[0396] 3 to 300 parts by mass, preferably 5 to 200 parts by mass, particularly preferably 10 to 120 parts by mass and especially preferably 15 to 90 parts by mass of at least one glass-based filler and / or reinforcing agent which can be used as component D), with the proviso that component B) is used in a lower mass fraction than component C).

[0397] The present invention particularly preferably relates to the use of the following compounds:

[0398] B) Aluminum methylphosphonate of formula (Ia)

[0399]

[0400] to achieve in or for a polyester-based product a CTI A of 600 according to IEC 60112-2010 and a laser transmittance of at least 8% determinable according to DVS Guideline 2243 (01 / 2014) at a wall thickness of 1.5 mm, wherein per 100 parts by mass of polyalkylene terephthalates or polycycloalkylene terephthalates, in particular polybutylene terephthalate, polyethylene terephthalate or poly-1,4-cyclohexanedimethanol terephthalate, 1 to 80 parts by mass, preferably 2 to 60 parts by mass, particularly preferably 3 to 30 parts by mass and especially preferably 5 to 20 parts by mass of an aluminum salt of the formula (Ia),

[0401] 5 to 120 parts by mass, preferably 7 to 80 parts by mass, particularly preferably 8 to 60 parts by mass, especially preferably 10 to 50 parts by mass of at least one organic phosphinate of the formula (II) and / or at least one diphosphinate of the formula (III) and / or polymers thereof which may be used as component C),

[0402]

[0403] in

[0404] R 1 , R 2 are identical or different and represent a linear or branched C1-C6-alkyl group and / or represent a C6-C 14 - aryl,

[0405] R 3 Represents linear or branched C1-C 10 -alkylene, C6-C 10 -arylene or C1-C6-alkyl-C6-C 10 -Arylene or C6-C 10 - aryl-C1-C6-alkylene,

[0406] M stands for aluminum, zinc or titanium,

[0407] m represents an integer from 1 to 4,

[0408] n represents an integer from 1 to 3,

[0409] x represents 1 and 2,

[0410] wherein n, x and m in formula (III) can simultaneously only be integers, so that the diphosphite of formula (III) as a whole is uncharged,

[0411] as well as

[0412] 3 to 300 parts by mass, preferably 5 to 200 parts by mass, particularly preferably 10 to 120 parts by mass and especially preferably 15 to 90 parts by mass of at least one glass-based filler and / or reinforcing agent which can be used as component D), with the proviso that component B) is used in a lower mass fraction than component C).

[0413] The invention finally provides the use of the composition according to the invention for producing products, preferably for electric vehicles, for household appliances and for products in the electronic and electrical field.

[0414] Other preferred compositions

[0415] The present invention provides a composition comprising:

[0416] A) per 100 parts by mass of polybutylene terephthalate, polyethylene terephthalate or poly-1,4-cyclohexanedimethanol terephthalate,

[0417] B) 1 to 80 parts by mass, preferably 2 to 60 parts by mass, particularly preferably 3 to 30 parts by mass, and especially preferably 5 to 20 parts by mass of aluminum methylphosphonate of the formula (Ia)

[0418]

[0419] C) 5 to 120 parts by mass, preferably 7 to 80 parts by mass, particularly preferably 8 to 60 parts by mass of aluminum tris(diethylphosphinate), and

[0420] D) 3 to 300 parts by mass, preferably 5 to 200 parts by mass, particularly preferably 10 to 120 parts by mass, and especially preferably 15 to 90 parts by mass of glass fibers,

[0421] The proviso is that component B) is present in a lower mass fraction than component C).

[0422] Very particular preference is given to using the following combination: polybutylene terephthalate as component A), aluminum methylphosphonate of the formula (Ia)

[0423]

[0424] as component B), aluminum tris(diethylphosphinate) as component C) and glass fibers as component D).

[0425] Other preferred methods

[0426] The present invention also provides a method for producing a product, preferably a method for electric vehicles, household appliances, and products in the electronic and electrical fields, the method comprising: reacting component A) 100 parts by weight of polybutylene terephthalate, polyethylene terephthalate or poly-1,4-cyclohexanedimethanol terephthalate with

[0427] B) 1 to 80 parts by mass, preferably 2 to 60 parts by mass, particularly preferably 3 to 30 parts by mass, and especially preferably 5 to 20 parts by mass of aluminum methylphosphonate of the formula (Ia)

[0428]

[0429] C) 5 to 120 parts by mass, preferably 7 to 80 parts by mass, particularly preferably 8 to 60 parts by mass of aluminum tris(diethylphosphinate), and

[0430] D) 3 to 300 parts by mass, preferably 5 to 200 parts by mass, particularly preferably 10 to 120 parts by mass, and especially preferably 15 to 90 parts by mass of glass fibers

[0431] and optionally mixed or blended with further additives in at least one mixing apparatus and finally processed by injection molding the resulting mixture, with the proviso that component B) is used in a lower mass fraction than component C).

[0432] Very particular preference is given to a process using polybutylene terephthalate as component A), aluminum methylphosphonate of the formula (Ia)

[0433]

[0434] as component B), aluminum tris(diethylphosphinate) as component C) and glass fibers as component D).

[0435] Example

[0436] In order to verify the improvement of the properties described according to the invention, the corresponding polymer compositions based on polyalkylene terephthalates or polycycloalkylene terephthalates were first produced by compounding. For this purpose, the individual components according to Table I were mixed in a twin-screw extruder (ZSK 25 compounder from Coperion Werner & Pfleiderer (Stuttgart, Germany) in a temperature range of 260° C. to 290° C., extruded, cooled until granulable, and granulated. After drying, usually after drying for 2 hours at 120° C. in a vacuum drying oven, the pellets were processed by injection molding in a temperature range of 260° C. to 290° C. to provide standard test specimens for the individual tests using an Arburg 320-210-500 injection molding machine.

[0437] The production of the methylphosphonic acid aluminum of the formula (Ia) used as component B) in the examples and comparative examples was carried out according to Example 1 of WO 2021 / 076169 A1.

[0438]

[0439] Tracking resistance

[0440] Based on IEC 60112-2010, the tracking resistance ("Relative Tracking Index") was determined with test solution A at a test voltage of 600 V using a test specimen with dimensions of 60 mm x 40 mm x 4 mm.

[0441] In contrast to the standard, the test was not carried out with 50 droplets on 5 test specimens in each case (250 droplets), but even more demandingly with 100 droplets on 3 test specimens in each case (300 droplets in total), and the average number of droplets until material failure due to tracking currents >0.5 A on the test specimens or ignition and subsequent continuous ignition was determined.

[0442] Laser transparency

[0443] The laser transparency of the samples investigated in the context of the present invention was measured in accordance with DVS guideline 2243 (01 / 2014) “Laser beam welding of thermoplastics” using test specimens with dimensions of 125 mm×13 mm×1.5 mm in the near infrared (NIR) range with a laser wavelength of 980 nm using a transmission meter LPKF TMG3 from LPKF Laser & Electronics AG (Garbsen, Germany) which had previously been calibrated using measurement standards produced in accordance with DIN EN ISO / IEC 17025, see: LPKF AG 101016-DE: “Simple transmission measurement LPKF TMG3 for plastics (Einfache Transmissionsmessung für Kunststoffe LPKF TMG3)”.

[0444] Flame retardant

[0445] The flame retardancy of test specimens having the dimensions of 125 mm x 13 mm x 0.75 mm was determined according to method UL94V (Underwriters Laboratories Safety Standard, "Test for Flammability of Plastic Materials for Parts of Equipment and Appliances", p. 14-18, Northbrook 1998).

[0446] IZOD impact resistance

[0447] IZOD impact resistance was determined according to ISO 180-A on test specimens with dimensions of 80 mm x 10 mm x 4 mm.

[0448] The flexural strength and external fiber strain were obtained from flexural tests performed according to ISO 178 on test specimens with dimensions of 80 mm x 10 mm x 4 mm.

[0449] Starting Materials:

[0450] Component A / 1): Linear polybutylene terephthalate (with an intrinsic viscosity of 93 cm in a 3:2 ratio) 3 / g (in each case, measured in phenol:1,2-dichlorobenzene=1:1 at 25°C) B 1300 mixture). The TRANSPAR® type is a commercially available product of Lanxess Deutschland GmbH (Cologne, Germany).

[0451] Component B / 1): Aluminum methylphosphonate of formula (Ia) produced according to WO 2021 / 076169 A1, Example 1

[0452] Component C / 1): Aluminum tris(diethylphosphinate), [CAS No. 225789-38-8] (from Clariant SE (Muttenz, Switzerland) OP1240)

[0453] Component D / 1): Chopped glass fibers CS7967D from Lanxess Deutschland GmbH (Cologne, Germany) [average fiber diameter 10 μm, average fiber length 4.5 mm, E glass (DIN 1259), silane-sized]

[0454] Component E): As further additives of component E), the following components commonly used for flame-retardant thermoplastic polyesters were used in the examples:

[0455] Anti-drip additive: polytetrafluoroethylene, [CAS No. 9002-84-0] (Dyneon PA 5932 from Dyneon GmbH & Co KG, Neuss, Germany)

[0456] Thermal stabilizer: Tetrakis(2,4-di-tert-butylphenyl)-1,1-biphenyl-4,4'-diyl-

[0457] bisphosphonite)[CAS No.38613-77-3](from Clariant International Ltd.

[0458] (Muttenz, Switzerland) P-EPQ)

[0459] Release agent: Pentaerythritol tetrastearate (PETS) [CAS No.115-83-3]

[0460] ( VPG 861, Cognis Deutschland GmbH, Düsseldorf, Germany)

[0461] For the respective comparative examples and examples, the further additives (component E) used were identical in type and amount in each case, ie totaling 1.0 part by mass.

[0462] Component X / 1): melamine cyanurate ( MC25, BASF SE, Ludwigshafen, Germany)

[0463] Table I

[0464] Example 1 Comparative Example 1 Comparative Example 2 Component A / 1 Quality score 100 100 100 Component B / 1 Quality score 9.5 0.0 0.0 Component C / 1 Quality score 27.6 27.6 37.1 Component D / 1 Quality score 34.5 34.5 34.5 Component E Quality score 1.0 1.0 1.0 Component X / 1 Quality score 0.0 9.5 0.0 UL94(0.75mm) [grade] V0 V0 - CTI A at 600V [Average number of droplets] 100 >50,<100 <50 IZOD <![CDATA[[kJ / m 2 ]]]> 35 <30 - Bending strength [MPa] 149 143 - External fiber strain [%] 2.8 <2.5 - LPKF laser transmittance [%] 9.7 <8 -

[0465] The components in Table I reported in parts by mass are based on 100 parts by mass of component A1.

[0466] Table 1 shows that only Example 1 of the present invention exhibits a UL94 V0 rating at 0.75 mm and achieves CTI A at 600 V using 100 droplets for 3 test samples in each case (300 droplets in total) under more severe conditions than the standard, and also exhibits a laser transmittance significantly higher than 8% for a 1.5 mm thick test sample.

[0467] Example 1 also exhibits better mechanical properties compared to the formulation containing a nitrogen-containing flame retardant (Comparative Example 1), as is evident, for example, from higher IZOD impact strength values ​​and better external fiber strain values.

Claims

1. A composition comprising: A) per 100 parts by mass of polyalkylene terephthalate or polycycloalkylene terephthalate, B) 1 to 80 parts by mass, preferably 2 to 60 parts by mass, particularly preferably 3 to 30 parts by mass, and especially preferably 5 to 20 parts by mass of at least one aluminum salt of the general formula (I) Where R represents C1-C 12 - alkyl, preferably represents methyl, ethyl, isopropyl or isobutyl, tert-butyl or n-butyl, particularly preferably represents ethyl or methyl, very particularly preferably represents methyl, C) 5 to 120 parts by mass, preferably 7 to 80 parts by mass, particularly preferably 8 to 60 parts by mass, especially preferably 10 to 50 parts by mass of at least one organic phosphinate of the formula (II) and / or at least one diphosphinate of the formula (III) and / or polymers thereof, in R 1 , R 2 are identical or different and represent a linear or branched C1-C6-alkyl group and / or a C6-C 14 - aryl, R 3 Represents linear or branched C1-C 10 -alkylene, C6-C 10 -arylene, or C1-C6-alkyl-C6-C 10 -arylene, or C6-C 10 - aryl-C1-C6-alkylene, M stands for aluminum, zinc or titanium, m represents an integer from 1 to 4, n represents an integer from 1 to 3, x represents 1 and 2, wherein n, x and m in formula (III) can simultaneously only be integers, so that the diphosphite of formula (III) as a whole is uncharged, and D) 3 to 300 parts by mass, preferably 5 to 200 parts by mass, particularly preferably 10 to 120 parts by mass, and especially preferably 15 to 90 parts by mass of at least one glass-based filler and / or reinforcing agent, The proviso is that component B) is present in a lower mass fraction than component C).

2. The composition according to claim 1, characterized in that The composition uses polybutylene terephthalate, polyethylene terephthalate, or poly-1,4-cyclohexanedimethanol terephthalate as component A).

3. The composition according to claim 1 or 2, characterized in that The composition uses aluminum tris(diethylphosphinate) as component C).

4. A composition according to one or more of claims 1 to 3, characterised in that The composition uses glass fibers as component D).

5. The composition according to one or more of claims 1 to 4, characterized in that The composition uses polybutylene terephthalate as component A), aluminum methylphosphonate of formula (Ia) as component B), aluminum tris(diethylphosphinate) as component C) and glass fibers as component D).

6. A product based on the composition according to one or more of claims 1 to 5, preferably for electric vehicles, for household appliances and for products in the electronic and electrical field.

7. A method for producing a product, preferably a product for electric vehicles, household appliances and products in the electronic and electrical fields, the method comprising: 100 parts by weight of component A) of polyalkylene terephthalate or polycycloalkylene terephthalate, and B) 1 to 80 parts by mass, preferably 2 to 60 parts by mass, particularly preferably 3 to 30 parts by mass, and especially preferably 5 to 20 parts by mass of at least one aluminum salt of the general formula (I) Where R represents C1-C 12 - alkyl, preferably represents methyl, ethyl, isopropyl or isobutyl, tert-butyl or n-butyl, particularly preferably represents ethyl or methyl, very particularly preferably represents methyl, C) 5 to 120 parts by mass, preferably 7 to 80 parts by mass, particularly preferably 8 to 60 parts by mass, especially preferably 10 to 50 parts by mass of at least one organic phosphinate of the formula (II) and / or at least one diphosphinate of the formula (III) and / or polymers thereof, in R 1 , R 2 are identical or different and represent a linear or branched C1-C6-alkyl group and / or a C6-C 14 - aryl, R 3 Represents linear or branched C1-C 10 -alkylene, C6-C 10 -arylene, or C1-C6-alkyl-C6-C 10 -arylene, or C6-C 10 - aryl-C1-C6-alkylene, M stands for aluminum, zinc or titanium, m represents an integer from 1 to 4, n represents an integer from 1 to 3, x represents 1 and 2, wherein n, x and m in formula (III) can simultaneously only be integers, so that the diphosphite of formula (III) as a whole is uncharged, and D) 3 to 300 parts by mass, preferably 5 to 200 parts by mass, particularly preferably 10 to 120 parts by mass, and especially preferably 15 to 90 parts by mass of at least one glass-based filler and / or reinforcing agent, and optionally mixed or blended with further additives in at least one mixing apparatus and finally processed by injection molding the resulting mixture, with the proviso that component B) is used in a lower mass fraction than component C).

8. The method according to claim 7, characterized in that The process uses polybutylene terephthalate, polyethylene terephthalate, or poly-1,4-cyclohexanedimethanol terephthalate as component A).

9. The method according to claim 7 or 8, characterized in that The process uses aluminum tris(diethylphosphinate) as component C).

10. Method according to one or more of claims 7 to 9, characterised in that The process uses glass fibers as component D).

11. Method according to one or more of claims 7 to 10, characterised in that The method uses polybutylene terephthalate as component A), aluminum methylphosphonate of formula (Ia) as component B), aluminum tris(diethylphosphinate) as component C) and glass fibers as component D).

12. Use of a composition according to one or more of claims 1 to 5 for producing products, preferably for electric vehicles, for household appliances and for products in the electronic and electrical field.

Citation Information

Patent Citations

  • Flame-retardant polyester compositions and their use

    DE102017215776A1

  • DE2035390A1

  • reinforced intergranular thermoplastic polyester compositions

    DE2248242A1

  • age-resistant thermoplastic molding compounds with good toughness

    DE3631539A1

  • thermoplastic molding compounds with high aging resistance and good low-temperature toughness

    DE3631540A1